Polymerizable liquid crystal composition, phase difference film, elliptically polarizing plate and optical display
A polymerizable liquid crystal composition with mixed molecular structures improves solubility, preventing precipitation and orientation defects, resulting in improved film quality and display performance.
Patent Information
- Application Number
- CN202180020034.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-11
- Filing Date
- 2021-03-04
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-03-04
AI Technical Summary
The solubility of polymerizable liquid crystal compounds in solvents is often inadequate, leading to precipitation and orientation defects in optical films, which affects film-forming properties and performance.
A polymerizable liquid crystal composition comprising at least two polymerizable liquid crystal compounds with different molecular structures but the same molecular weight, specifically including 1,4-trans-cyclohexanediyl and 1,4-cis-cyclohexanediyl groups, enhances solubility and reduces precipitation, thereby improving film quality.
The composition ensures high solubility in solvents, preventing undissolved compounds from precipitating and causing orientation defects, thus enhancing the stability and performance of phase difference films and elliptically polarizing plates in optical displays.
Smart Images

Figure BDA0003838634820000031 
Figure BDA0003838634820000041 
Figure BDA0003838634820000111
Abstract
Description
Technical Field
[0001] The present invention relates to a polymerizable liquid crystal composition, a phase difference film composed of a cured product of the polymerizable liquid crystal composition, and an elliptically polarizing plate and an optical display including the phase difference film. Background Art
[0002] As an optical film such as a phase difference film used in a flat panel display device (FPD), there is an optical film obtained by applying a coating liquid obtained by dissolving a polymerizable liquid crystal compound in a solvent to a supporting substrate and then polymerizing it. As a polymerizable liquid crystal compound used to form such an optical film, for example, a nematic liquid crystal compound having a rod-like structure formed by connecting 2 to 4 6-membered rings is known.
[0003] On the other hand, as one of the characteristics of a retardation film, it is required to be able to perform the same polarization conversion in the entire wavelength range. For example, it is known that in a wavelength range where the value [Re(λ) / Re(550)] obtained by dividing the retardation value Re(λ) at a certain wavelength λ by the retardation value Re(550) at 550nm is close to 1, and in a wavelength range showing reverse wavelength dispersion of [Re(450) / Re(550)]<1, the same polarization conversion can be performed in theory. Polymerizable liquid crystal compounds that can constitute such a retardation film are disclosed in, for example, Patent Documents 1 and 2.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-207765
[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-143788 Summary of the invention
[0008] Problems to be solved by the invention
[0009] In the solution (coating liquid) obtained by dissolving a polymerizable liquid crystal compound in a solvent for manufacturing an optical film, sometimes the solubility in various solvents is lacking due to the molecular structure of the polymerizable liquid crystal compound. Such a polymerizable liquid crystal compound with low solubility sometimes precipitates in the coating liquid or crystallizes and precipitates, and the precipitation and precipitation of such a polymerizable liquid crystal compound will not only cause the film-forming property to decrease, but also cause the orientation defects in the obtained optical film. Therefore, it is expected to develop a polymerizable liquid crystal composition comprising a polymerizable liquid crystal that shows further improved solubility in the solvent.
[0010] An object of the present invention is to provide a polymerizable liquid crystal composition having excellent solubility in a solvent.
[0011] Means for solving problems
[0012] The present invention provides the following preferred embodiments.
[0013] [1] A polymerizable liquid crystal composition comprising at least two polymerizable liquid crystal compounds having the same molecular weight but different molecular structures and represented by formula (1),
[0014] [Chemical formula 1]
[0015] P 1 -F 1 -B 1 -A 1 -E 1 -G 1 -D 1 -Ar-D 2 -G 2 -E 2 -A 2 -B 2 -F 2 -P 2 (1)
[0016] [In formula (1),
[0017] Ar represents a divalent aromatic hydrocarbon group or a divalent aromatic heterocyclic group which may have a substituent,
[0018] D 1 , D 2 、E 1 、E 2 , B 1 and B 2 Each independently represents -CR 11 R 12 -, -CH2-CH2-, -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -C(=S)-O-, -OC(=S)-, -OC(=S)-O-, -CO-NR 11 -、-NR 11 -CO-, -O-CH2-, -CH2-O-, -S-CH2-, -CH2-S- or a single bond, R 11 and R 12 each independently represents a hydrogen atom, a fluorine atom or an alkyl group having 1 to 4 carbon atoms,
[0019] G 1 and G 2 Each represents a 1,4-cyclohexanediyl group,
[0020] A 1 and A 2Each independently represents a divalent alicyclic hydrocarbon group having 3 to 16 carbon atoms or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms, and the hydrogen atoms contained in the alicyclic hydrocarbon group and the aromatic hydrocarbon group may be halogen atoms, -R 13 、-OR 13 , cyano or nitro substituted, R 13 represents an alkyl group having 1 to 4 carbon atoms, wherein the hydrogen atoms contained in the alkyl group may be substituted by fluorine atoms,
[0021] F 1 and F 2 Each independently represents an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atom contained in the alkanediyl group may be -OR 14 or halogen atom substitution, R 14 represents an alkyl group having 1 to 4 carbon atoms, the hydrogen atoms contained in the alkyl group may be substituted by fluorine atoms, and the -CH2- contained in the alkanediyl group may be substituted by -O- or -CO-,
[0022] P 1 and P 2 Each independently represents a hydrogen atom or a polymerizable group (wherein P 1 and P 2 At least one of them is a polymerizable group)]
[0023] In the polymerizable liquid crystal composition, as the aforementioned polymerizable liquid crystal compound, G in formula (1) is included 1 and G 2 A polymerizable liquid crystal compound (1-1) each of which is a 1,4-trans-cyclohexanediyl group, and a polymerizable liquid crystal compound (1-1) having only the G in the formula (1) 1 and G 2 a polymerizable liquid crystal compound (1-2) having a different molecular structure in that at least one of the compounds is a 1,4-cis-cyclohexanediyl group,
[0024] The ratio of the peak area of the polymerizable liquid crystal compound (1-2) to the total peak area of the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) measured by liquid chromatography is 0.01% to 10%.
[0025] [2] The polymerizable liquid crystal composition according to [1] above, wherein the polymerizable liquid crystal compound (1-2) comprises G in the formula (1): 1 and G 2 A polymerizable liquid crystal compound (1-2a) in which any one of the above is 1,4-cis-cyclohexanediyl, and G in the formula (1) 1 and G 2 All of them are polymerizable liquid crystal compounds (1-2b) of 1,4-cis-cyclohexanediyl.
[0026] [3] The polymerizable liquid crystal composition according to [1] or [2], wherein Ar in formula (1) is a group represented by any one of formulas (2-1) to (2-5).
[0027] [Chemical formula 2]
[0028]
[0029] [Wherein,
[0030] * indicates the same as D 1 or D 2 The bonding portion;
[0031] Q 1 Indicates -S-, -O-, or -NR 15 -, R 15 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent,
[0032] Q 2 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent;
[0033] W 1 and W 2 Each independently represents -O-, -S-, -CO-, -NR 15 -, R 15 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent;
[0034] Y 1 represents an alkyl group having 1 to 6 carbon atoms, an aromatic hydrocarbon group or an aromatic heterocyclic group which may have a substituent, wherein the hydrogen atom contained in the alkyl group, the aromatic hydrocarbon group or the aromatic heterocyclic group may be substituted by a halogen atom, and the -CH2- contained in the alkyl group may be replaced by -O-, -CO-, -O-CO- or -CO-O-,
[0035] Y 2 represents a CN group or an alkyl group having 1 to 12 carbon atoms which may have a substituent, wherein the hydrogen atom contained in the alkyl group may be substituted by a halogen atom, and the -CH2- contained in the alkyl group may be replaced by -O-, -CO-, -O-CO- or -CO-O-;
[0036] Z 1 , Z 2 and Z 3 each independently represents a hydrogen atom, an aliphatic hydrocarbon group or alkoxy group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 3 to 20 carbon atoms, a monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -NR 15 R 16 or -SR 15 , Z1 and Z 2 can be bonded to each other to form an aromatic ring or an aromatic heterocyclic ring, R 15 and R 16 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms;
[0037] Ax represents an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocyclic rings, Ay represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a substituent, or an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocyclic rings, and Ax and Ay may be bonded to form a ring;
[0038] Y 3 and Y 4 Each independently represents a group selected from the following formula (Y-1).
[0039] [Chemical formula 3]
[0040]
[0041] [In formula (Y-1),
[0042] M 1 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted by one or more substituents X 3 Substitution, Substituent X 3 represents a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a pentafluorosulfur group, a nitro group, a cyano group, an isocyano group, an amino group, a hydroxyl group, a mercapto group, a methylamino group, a dimethylamino group, a diethylamino group, a diisopropylamino group, a trimethylsilyl group, a dimethylsilyl group, a thioisocyano group, group), or one -CH2- or two or more non-adjacent -CH2- are each independently replaced by -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NH-CO-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-, a linear or branched alkyl group having 1 to 20 carbon atoms, any hydrogen atom in the alkyl group may be substituted by a fluorine atom, or may be -B 11 -F 11 -P 11 The group represented by B 11 、F 11 and P 11Each of them is the same as B in the above formula (1) 1 、F 1 and P 1 Similarly defined, each can be combined with the above B 1 、F 1 and P 1 Same or different;
[0043] U 1 represents an organic group having 2 to 30 carbon atoms and having an aromatic hydrocarbon group, wherein any carbon atom of the aromatic hydrocarbon group may be replaced by a heteroatom, and the aromatic hydrocarbon group may be substituted by one or more of the above-mentioned substituents X 3 replace;
[0044] T 1 Indicates -O-, -S-, -COO-, -OCO-, -OCO-O-, -NU 2 -、-N=CU 2 -、-CO-NU 2 -、-OCO-NU 2 -or-O-NU 2 -,U 2 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, a cycloalkenyl group having 3 to 12 carbon atoms, an organic group having 2 to 30 carbon atoms having an aromatic hydrocarbon group (any carbon atom of the aromatic hydrocarbon group may be replaced by a heteroatom), or (E 11 -A 11 ) q -B 12 -F 12 -P 12 The alkyl, cycloalkyl, cycloalkenyl and aromatic hydrocarbon groups are each unsubstituted or may be substituted with one or more substituents X 3 The alkyl group may be substituted with the cycloalkyl or cycloalkenyl group, one -CH2- or two or more non-adjacent -CH2- in the alkyl group may be replaced with -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -SO2-, -O-CO-O-, -CO-NH-, -NH-CO-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-, one -CH2- or two or more non-adjacent -CH2- in the cycloalkyl or cycloalkenyl group may be replaced with -O-, -CO-, -COO-, -OCO- or -O-CO-O-, E 11 , A 11 , B 12 、F 12 and P 12Each of them is equal to E in formula (1) 1 , A 1 , B 1 、F 1 and P 1 Similarly defined, each can be combined with the above E 1 , A 1 , B 1 、F 1 and P 1 are the same or different, q represents an integer from 0 to 4, E 11 and / or A 11 When there are multiple, each may be the same or different. 1 with U 2 Can be bonded to form a ring
[0045] [4] The polymerizable liquid crystal composition according to any one of [1] to [3], wherein A in formula (1) 1 and A 2 Each is independently 1,4-cyclohexanediyl or 1,4-phenylenediyl.
[0046] [5] The polymerizable liquid crystal composition according to any one of [1] to [4], wherein P in formula (1) 1 and P 2 Each is an acryloyl group.
[0047] [6] The polymerizable liquid crystal composition according to any one of [1] to [5] above, further comprising a photopolymerization initiator.
[0048] [7] The polymerizable liquid crystal composition according to any one of [1] to [6] above, further comprising an organic solvent.
[0049] [8] A retardation film comprising a liquid crystal cured film, wherein the liquid crystal cured film is a cured product of the polymerizable liquid crystal composition according to any one of [1] to [7].
[0050] [9] The phase difference film according to [8] above, wherein the liquid crystal cured film satisfies the formula (i).
[0051] 0.75≤Re(450) / Re(550)<1.00(i)
[0052] [In formula (i), Re(λ) represents the in-plane phase difference value of the liquid crystal cured film at a wavelength of λ nm]
[0053]
[10] An elliptically polarizing plate comprising the phase difference film described in [8] or [9] above.
[0054]
[11] An optical display comprising the elliptically polarizing plate described in
[10] above.
[0055]
[12] A flexible image display device comprising the elliptically polarizing plate described in
[10] above.
[0056] Effects of the Invention
[0057] According to the present invention, a polymerizable liquid crystal composition having excellent solubility in a solvent can be provided. DETAILED DESCRIPTION
[0058] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made within the scope that does not impair the gist of the present invention.
[0059] <Polymerizable Liquid Crystal Composition>
[0060] The polymerizable liquid crystal composition of the present invention comprises at least two polymerizable liquid crystal compounds having the same molecular weight but different molecular structures and represented by formula (1). By comprising at least two polymerizable liquid crystal compounds having different molecular structures but the same molecular weight and similar molecular structures represented by formula (1), high solubility in a solvent can be ensured.
[0061] [Chemical formula 4]
[0062] P 1 -F 1 -B 1 -A 1 -E 1 -G 1 -D 1 -Ar-D 2 -G 2 -E 2 -A 2 -B 2 -F 2 -P 2 (1)
[0063] [In formula (1),
[0064] Ar represents a divalent aromatic hydrocarbon group or a divalent aromatic heterocyclic group which may have a substituent,
[0065] D 1 , D 2 、E 1 、E 2 , B 1 and B 2 Each independently represents -CR 11 R 12-, -CH2-CH2-, -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -C(=S)-O-, -OC(=S)-, -OC(=S)-O-, -CO-NR 11 -、-NR 11 -CO-, -O-CH2-, -CH2-O-, -S-CH2-, -CH2-S- or a single bond, R 11 and R 12 each independently represents a hydrogen atom, a fluorine atom or an alkyl group having 1 to 4 carbon atoms,
[0066] G 1 and G 2 Each represents a 1,4-cyclohexanediyl group,
[0067] A 1 and A 2 Each independently represents a divalent alicyclic hydrocarbon group having 3 to 16 carbon atoms or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms, and the hydrogen atoms contained in the alicyclic hydrocarbon group and the aromatic hydrocarbon group may be halogen atoms, -R 13 、-OR 13 , cyano or nitro substituted, R 13 represents an alkyl group having 1 to 4 carbon atoms, wherein the hydrogen atoms contained in the alkyl group may be substituted by fluorine atoms,
[0068] F 1 and F 2 Each independently represents an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atom contained in the alkanediyl group may be -OR 14 or halogen atom substitution, R 14 represents an alkyl group having 1 to 4 carbon atoms, the hydrogen atoms contained in the alkyl group may be substituted by fluorine atoms, and the -CH2- contained in the alkanediyl group may be substituted by -O- or -CO-,
[0069] P 1 and P 2 Each independently represents a hydrogen atom or a polymerizable group (wherein P 1 and P 2 At least one of them is a polymerizable group)].
[0070] In the polymerizable liquid crystal composition of the present invention, as the at least two polymerizable liquid crystal compounds, G in formula (1) 1 and G 2 A polymerizable liquid crystal compound (1-1) each of which is a 1,4-trans-cyclohexanediyl group (hereinafter, also referred to as a "polymerizable liquid crystal compound (1-1)"), and the polymerizable liquid crystal compound (1-1) described above having only G in the formula (1) 1 and G 2A polymerizable liquid crystal compound (1-2) having a different molecular structure in that at least one of the polymerizable liquid crystal compounds (1-1) is 1,4-cis-cyclohexanediyl (hereinafter, also referred to as "polymerizable liquid crystal compound (1-2)"). In the present invention, the polymerizable liquid crystal composition may contain only one polymerizable liquid crystal compound (1-1), or may contain two or more polymerizable liquid crystal compounds (1-1). In the case of containing multiple polymerizable liquid crystal compounds (1-1), the polymerizable liquid crystal composition of the present invention may contain a polymerizable liquid crystal compound (1-2) corresponding to at least one of the polymerizable liquid crystal compounds (1-1), or may contain polymerizable liquid crystal compounds (1-2) corresponding to each of the multiple polymerizable liquid crystal compounds (1-1) constituting the polymerizable liquid crystal composition.
[0071] By combining the polymerizable liquid crystal compound (1-1) and only G in the formula (1) 1 and G 2 The polymerizable liquid crystal compound (1-2) having a different molecular structure in that at least one of them is 1,4-cis-cyclohexanediyl, i.e., an isomer, can improve the solubility of the polymerizable liquid crystal compound (1-1) in a solvent. That is, in the case where the combination includes a polymerizable liquid crystal compound (1-1) and a polymerizable liquid crystal compound (1-2), more polymerizable liquid crystal compound (1-1) can be easily dissolved relative to the same amount or less amount of solvent compared to the case where the polymerizable liquid crystal compound (1-1) is dissolved alone in a solvent. As a result, it is not easy for undissolved polymerizable liquid crystal compounds to remain in the coating liquid, and in addition, the precipitation, precipitation, and stacking of the polymerizable liquid crystal compound in the coating liquid can be suppressed. The improvement of the solubility of the polymerizable liquid crystal compound (1-1) in a solvent is related to the suppression of orientation defects caused by undissolved polymerizable liquid crystal compounds, precipitates, etc., and the improvement of storage stability.
[0072] The polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) are each a polymerizable liquid crystal compound represented by formula (1).
[0073] [Chemical formula 5]
[0074] P 1 -F 1 -B 1 -A 1 -E 1 -G 1 -D 1 -Ar-D 2 -G 2 -E 2 -A 2 -B 2 -F 2 -P 2 (1)
[0075] The compound having the structure shown in formula (1) is usually a polymerizable liquid crystal compound that exhibits reverse wavelength dispersion when polymerized in a unidirectionally oriented state, and can perform the same polarization conversion in a wide wavelength region. Therefore, by using the polymerizable liquid crystal compound represented by formula (1), a polymerizable liquid crystal composition that can impart good display characteristics when a phase difference film or an elliptically polarizing plate formed by the polymerizable liquid crystal compound is used in an optical display such as a display device can be obtained.
[0076] In formula (1), G 1 and G 2 Each independently represents a 1,4-cyclohexanediyl group. The two polymerizable liquid crystal compounds (1-1) and the polymerizable liquid crystal compound (1-2) constituting the polymerizable liquid crystal composition of the present invention have G in the formula (1) 1 and G 2 The structures represented are all 1,4-trans-cyclohexanediyl or G 1 and G 2 The groups are different from each other in that any one or all of them are 1,4-cis-cyclohexanediyl groups.
[0077] In formula (1), D 1 , D 2 、E 1 、E 2 , B 1 and B 2 Each independently represents -CR 11 R 12 -, -CH2-CH2-, -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -C(=S)-O-, -OC(=S)-, -OC(=S)-O-, -CO-NR 11 -、-NR 11 -CO-, -O-CH2-, -CH2-O-, -S-CH2-, -CH2-S-, or a single bond. 11 and R 12 Each independently represents a hydrogen atom, a fluorine atom or an alkyl group having 1 to 4 carbon atoms, and is preferably a hydrogen atom, a methyl group or an ethyl group.
[0078] In formula (1), D 1 and D 2 Each of them is independently preferably -CO-O-, -O-CO-, -C(=S)-O-, -OC(=S)-, -O-CH2-, -CH2-O-, -CO-NR 11 -or-NR 11 -CO-, more preferably -CO-O-, -O-CO-, -CO-NR 11 -or-NR11 -CO-, particularly preferably -CO-O- and -O-CO-. 11 It is preferably a hydrogen atom, a methyl group or an ethyl group. 1 and D 2 can be the same or different from each other. It should be noted that the so-called D 1 With D 2 The same as each other means that D when Ar is regarded as the center 1 With D 2 The structures are the same as each other. 1 With E 2 , A 1 With A 2 , B 1 With B 2 , and F 1 With F 2 The same is true for the relationship.
[0079] In formula (1), E 1 、E 2 , B 1 and B 2 Each of them is independently preferably -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO-NR 11 -、-NR 11 -CO- or a single bond, more preferably -O-, -O-CO- or -CO-O-. 11 It is preferably a hydrogen atom, a methyl group or an ethyl group. 1 With E 2 , and B 1 With B 2 May be the same as or different from each other.
[0080] In formula (1), A 1 and A 2 Each independently represents a divalent alicyclic hydrocarbon group having 3 to 16 carbon atoms or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms. Here, the hydrogen atoms contained in the alicyclic hydrocarbon group and the aromatic hydrocarbon group may be replaced by halogen atoms, -R 13 、-OR 13 , cyano or nitro substituted, R 13 It represents an alkyl group having 1 to 4 carbon atoms, and hydrogen atoms contained in the alkyl group may be substituted by fluorine atoms.
[0081] In formula (1), A 1 and A 2Each is independently preferably 1,4-phenylenediyl which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, or 1,4-cyclohexanediyl which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms. More preferably, it is 1,4-phenylenediyl substituted with a methyl group, unsubstituted 1,4-phenylenediyl, or unsubstituted 1,4-cyclohexanediyl. It is particularly preferably unsubstituted 1,4-phenylenediyl or unsubstituted 1,4-cyclohexanediyl, and particularly preferably unsubstituted 1,4-phenylenediyl. In formula (1), A 1 and A 2 May be the same as or different from each other.
[0082] In formula (1), F 1 and F 2 Each independently represents an alkanediyl group having 1 to 12 carbon atoms. Here, the hydrogen atoms contained in the alkanediyl group may be -OR 14 or halogen atom substitution, R 14 represents an alkyl group having 1 to 4 carbon atoms, wherein the hydrogen atoms contained in the alkyl group may be substituted by fluorine atoms. In addition, -CH2- contained in the alkanediyl group may be replaced by -O- or -CO- (wherein, when there are multiple -O- groups, they are not adjacent to each other).
[0083] In formula (1), F 1 and F 2 Each of them is independently preferably an alkanediyl group having 4 to 12 carbon atoms which may be substituted. 1 and F 2 May be the same as or different from each other.
[0084] As P 1 or P 2 The polymerizable group represented by may include epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyl, methacryloyl, oxirane and oxetanyl. Among them, acryloyl, methacryloyl, vinyl and vinyloxy are preferred, acryloyl and methacryloyl are more preferred, and acryloyl is still more preferred. In formula (1), P 1 and P 2 As long as any one of them is a polymerizable group, they may be the same or different from each other, but preferably 1 and P 2 are polymerizable groups, preferably P 1 and P 2 All are acryloyl.
[0085] In formula (1), Ar represents a divalent aromatic hydrocarbon group or a divalent aromatic heterocyclic group which may have a substituent. In the present invention, a divalent aromatic hydrocarbon group which may have a substituent refers to a divalent linking group containing at least one aromatic hydrocarbon ring, and a divalent aromatic heterocyclic group which may have a substituent refers to a divalent linking group containing at least one aromatic heterocyclic ring. The aromatic hydrocarbon ring and aromatic heterocyclic ring referred to herein refer to a ring structure having a number of π electrons of [4n+2] (n represents an integer) according to the Huckel rule (in the case of an aromatic heterocyclic ring, the Huckel rule is satisfied including non-covalent bond electron pairs on heteroatoms such as -N= and -S-). Ar may contain one aromatic hydrocarbon ring or aromatic heterocyclic ring, or may contain two or more aromatic hydrocarbon rings or aromatic heterocyclic rings. When containing one aromatic hydrocarbon ring or aromatic heterocyclic ring, Ar may be a divalent aromatic hydrocarbon group which may have a substituent, or may be a divalent aromatic heterocyclic group which may have a substituent. When containing two or more aromatic hydrocarbon rings or aromatic heterocycles, it may contain a plurality of only aromatic hydrocarbon rings, or only aromatic heterocycles, or may contain one or more each of aromatic hydrocarbon rings and aromatic heterocycles. Two or more aromatic hydrocarbon rings and / or aromatic heterocycles may be bonded to each other by a single bond, -CO-O-, -O- or other divalent bonding groups.
[0086] As the aromatic hydrocarbon ring that can be included in Ar, for example, benzene ring, naphthalene ring, anthracene ring etc. can be enumerated, preferably benzene ring, naphthalene ring.As aromatic heterocycle, furan ring, benzofuran ring, pyrrole ring, indole ring, thiophene ring, benzothiophene ring, pyridine ring, pyrazine ring, pyrimidine ring, triazole ring, triazine ring, pyrroline ring, imidazole ring, pyrazole ring, thiazole ring, benzothiazole ring, thienothiazole (thienothiazole) ring, oxazole ring, benzoxazole ring and phenanthroline ring etc. can be enumerated.In the case of including nitrogen atom in Ar, the nitrogen atom preferably has π electrons.
[0087] Among them, Ar preferably has an aromatic heterocyclic ring containing at least two heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms and sulfur atoms, more preferably has a thiazole ring, a benzothiazole ring or a benzofuran ring, and further preferably has a benzothiazole ring. It should be noted that when Ar has an aromatic heterocyclic ring containing at least two heteroatoms selected from the group consisting of nitrogen atoms, oxygen atoms and sulfur atoms, the aromatic heterocyclic ring may be combined with D in formula (1) 1 and D 2 Directly bonded to form a divalent linking group, it can also be used as a 1 and D 2 The Ar group including the aromatic heterocyclic ring is preferably included as a substituent of a divalent linking group directly bonded thereto, but the Ar group including the aromatic heterocyclic ring is preferably sterically arranged in a direction substantially orthogonal to the molecular orientation direction as a whole.
[0088] In formula (1), the total number of π electrons N contained in the divalent aromatic hydrocarbon group or divalent aromatic heterocyclic group which may have a substituent represented by Ar is π It is preferably 8 or more, more preferably 12 or more, particularly preferably 16 or more, and particularly preferably 20 or more. It is preferably 36 or less, more preferably 32 or less, further preferably 30 or less, particularly preferably 26 or less, and particularly preferably 24 or less.
[0089] Examples of the optionally substituted divalent aromatic hydrocarbon group or divalent aromatic heterocyclic group represented by Ar in the formula (1) include groups represented by the following formulae (2-1) to (2-5).
[0090] [Chemical formula 6]
[0091]
[0092] In formulas (2-1) to (2-5), * represents the 1 or D 2 The bonding portion.
[0093] In formula (2-1), Q 1 Indicates -S-, -O-, or -NR 15 -, R 15 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent. 2 It represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent.
[0094] In formula (2-2), W 1 and W 2 Each independently represents -O-, -S-, -CO-, -NR 15 -, R 15 It represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent.
[0095] In formula (2-1), Y 1 represents an alkyl group having 1 to 6 carbon atoms, an aromatic hydrocarbon group or an aromatic heterocyclic group which may have a substituent, preferably an aromatic hydrocarbon group having 6 to 12 carbon atoms or an aromatic heterocyclic group having 3 to 12 carbon atoms which may have a substituent, and more preferably an aromatic hydrocarbon group having 6 to 12 carbon atoms or an aromatic heterocyclic group having 3 to 12 carbon atoms. In formula (2-2), Y 2 It represents a CN group or an alkyl group having 1 to 12 carbon atoms which may have a substituent. Here, the hydrogen atom contained in the alkyl aromatic heterocyclic group or the aromatic heterocyclic group may be substituted by a halogen atom, and the -CH2- contained in the alkyl group may be replaced by -O-, -CO-, -O-CO- or -CO-O-.
[0096] In formulas (2-1) to (2-5), Z 1 , Z 2 and Z 3 each independently represents a hydrogen atom, an aliphatic hydrocarbon group or alkoxy group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 3 to 20 carbon atoms, a monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -NR 15 R 16 or -SR 15 , Z 1 and Z 2 They may be bonded to each other to form an aromatic ring or an aromatic heterocyclic ring. 15 and R 16 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0097] In formulas (2-3) and (2-4), Ax represents an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocyclic rings, and Ay represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a substituent, or an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocyclic rings, and Ax and Ay may be bonded to form a ring.
[0098] The groups represented by formulae (2-1) to (2-4) are not particularly limited, and specific examples thereof include groups described in JP-A-2011-207765, JP-A-2008-107767, WO2014 / 010325, and the like.
[0099] In formula (2-5), Y 3 and Y 4 Each is independently selected from the group represented by the following formula (Y-1).
[0100] [Chemical formula 7]
[0101]
[0102] In formula (Y-1), M 1 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. The alkyl group may be substituted by one or more substituents X 3 replace.
[0103] Substituent X 3represents a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a sulfur pentafluoride group, a nitro group, a cyano group, an isocyano group, an amino group, a hydroxyl group, a mercapto group, a methylamino group, a dimethylamino group, a diethylamino group, a diisopropylamino group, a trimethylsilyl group, a dimethylsilyl group, a thioisocyano group, or one -CH2- or two or more non-adjacent -CH2- are each independently replaced by -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NH-CO-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-, and any hydrogen atom in the alkyl group may be substituted by a fluorine atom, or may be -B 11 -F 11 -P 11 The group represented by B 11 、F 11 and P 11 Each of them is the same as B in the above formula (1) 1 、F 1 and P 1 Similarly defined, each can be combined with the above B 1 、F 1 and P 1 Same or different.
[0104] As a substituent X 3 , preferably a fluorine atom, a chlorine atom, -CF3, -OCF3 or a cyano group. 1 It is preferably an unsubstituted or hydrogen atom or an alkyl group having 1 to 6 carbon atoms substituted with one or more fluorine atoms, and more preferably a hydrogen atom.
[0105] U 1 represents an organic group having 2 to 30 carbon atoms and having an aromatic hydrocarbon group. Any carbon atom of the aromatic hydrocarbon group may be replaced by a heteroatom. 1 is an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocyclic rings. The aromatic hydrocarbon group may be substituted with one or more of the above-mentioned substituents X 3 replace.
[0106] From the perspective of improving wavelength dispersion, U 1 Preferably, it is an organic group having an aromatic heterocyclic ring in which one or more carbon atoms are replaced by heteroatoms. In order to obtain good wavelength dispersion and high birefringence, U 1 More preferably, it is an organic group having an aromatic heterocyclic ring which is a condensed ring of a 5-membered ring and a 6-membered ring.
[0107] Specifically, as U 1 , preferably an organic group having a group represented by the following formula. It should be noted that in the following formula, these groups have a T at any position 1 connection key.
[0108] [Chemical formula 8]
[0109]
[0110] T 1 Indicates -O-, -S-, -COO-, -OCO-, -OCO-O-, -NU 2 -、-N=CU 2 -、-CO-NU 2 -、-OCO-NU 2 -or-O-NU 2 -,U 2 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, a cycloalkenyl group having 3 to 12 carbon atoms, an organic group having 2 to 30 carbon atoms having an aromatic hydrocarbon group (any carbon atom of the aromatic hydrocarbon group may be replaced by a heteroatom), or (E 11 -A 11 ) q -B 12 -F 12 -P 12 The aforementioned alkyl, cycloalkyl, cycloalkenyl and aromatic hydrocarbon groups are each unsubstituted or may be substituted with one or more substituents X. 3 The aforementioned alkyl group may be substituted with the aforementioned cycloalkyl group or the aforementioned cycloalkenyl group. One -CH2- or two or more non-adjacent -CH2- in the aforementioned alkyl group may be replaced with -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -SO2-, -O-CO-O-, -CO-NH-, -NH-CO-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-, and one -CH2- or two or more non-adjacent -CH2- in the aforementioned cycloalkyl group or cycloalkenyl group may be replaced with -O-, -CO-, -COO-, -OCO- or O-CO-O-. 11 , A 11 , B 12 、F 12 and P 12 Each of them is the same as E in the above formula (1) 1 , A 1 , B 1 、F 1and P 1 Similarly defined, each can be combined with the above E 1 , A 1 , B 1 、F 1 and P 1 are the same or different, q represents an integer from 0 to 4, E 11 and / or A 11 When there are plural of them, they may be the same or different.
[0111] Considering the good birefringence and easy synthesis, T 1 Preferred are -O-, -S-, -N=CU 2 -or-NU 2 -, from the perspective of easily improving wavelength dispersion and birefringence, T 1 More preferably, it is -O-, -S- or -NU 2 -.
[0112] U 2 Preferably, it may be substituted by one or more of the above-mentioned substituents X 3 Substituted, and one -CH2- or two or more non-adjacent -CH2- can be replaced independently by -O-, -CO-, -COO-, -OCO- or -O-CO-O-, an alkyl or alkenyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or a cycloalkenyl group having 3 to 12 carbon atoms; or the aforementioned alkyl or alkenyl group can be substituted by the cycloalkyl group, cycloalkenyl group or aryl group.
[0113] Among them, from the perspective of birefringence and solvent solubility, U 2 More preferably, a straight-chain alkyl group having 1 to 20 carbon atoms in which a hydrogen atom may be substituted with a fluorine atom and one -CH2- or two or more non-adjacent -CH2- may each independently be replaced with -O-, -CO-, -COO- or -OCO-.
[0114] U 1 with U 2 In this case, for example, -NU 1 U 2 Cyclic group, or -N=CU 1 U 2 Represents a cyclic group.
[0115] Y is easy to obtain from raw materials, has good solubility and shows high birefringence. 3 and Y 4 Each particularly preferably represents a group selected from the following formula (Y-1′) to formula (Y-47′).
[0116] [Chemical formula 9]
[0117]
[0118] [Chemical formula 10]
[0119]
[0120] The molecular structure of the polymerizable liquid crystal compound (1) is preferably symmetrical from the viewpoint of improving the orientation of the polymerizable liquid crystal compound (1), facilitating industrial production and improving productivity. The group represented by the formula (2-5) includes the following groups. The * in the following (2-5a) to (2-5t) indicates that the polymerizable liquid crystal compound (1) is symmetrical. 1 or D 2 The bonding portion.
[0121] [Chemical formula 11]
[0122]
[0123] [Chemical formula 12]
[0124]
[0125] [Chemical formula 13]
[0126]
[0127] Among formulas (2-1) to (2-5), formula (2-1), formula (2-3), formula (2-4) and formula (2-5) are preferred, formula (2-1) and formula (2-5) are more preferred, and formula (2-1) is particularly preferred.
[0128] In the present invention, examples of the polymerizable liquid crystal compound represented by formula (1) include compounds described in JP-A-2019-003177 and JP-A-2019-073496.
[0129] The polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) constituting the polymerizable liquid crystal composition of the present invention have a structure represented by the above formula (1) only in G 1 and G 2 The structures of the 1,4-cyclohexanediyl groups represented by the polymerizable liquid crystal compound (1-1) are different from each other. 1 and G 2 Based on the structure of the polymerizable liquid crystal compound (1-1), the polymerizable liquid crystal compound (1-2) is different from the polymerizable liquid crystal compound (1-1) only in G 1 and G 2The difference is that at least one of them is 1,4-cis-cyclohexanediyl.
[0130] In the present invention, the polymerizable liquid crystal compound (1-2) may be G in formula (1): 1 and G 2 A polymerizable liquid crystal compound (1-2a) in which one of the two is 1,4-trans-cyclohexanediyl and the other is 1,4-cis-cyclohexanediyl (hereinafter, also referred to as “polymerizable liquid crystal compound (1-2a)”), or G in formula (1) 1 and G 2 The polymerizable liquid crystal compound (1-2b) (hereinafter also referred to as "polymerizable liquid crystal compound (1-2b)") is a 1,4-cis-cyclohexanediyl group. The polymerizable liquid crystal composition of the present invention may contain only one of the polymerizable liquid crystal compound (1-2a) and the polymerizable liquid crystal compound (1-2b), or may contain both of them.
[0131] The polymerizable liquid crystal composition of the present invention comprises a polymerizable liquid crystal composition (1-1) and a polymerizable liquid crystal compound (1-2) in an amount such that the ratio of the peak area of the polymerizable liquid crystal compound (1-2) to the total peak area of the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) measured by liquid chromatography (hereinafter also referred to as "area percentage value") is 0.01% to 10%. For a polymerizable liquid crystal compound represented by formula (1) having a so-called T-shaped structure in which constituent molecules are arranged in the long axis direction of the main chain of the compound and in a direction intersecting the long axis direction, G in formula (1) 1 and G 2 When all of them are 1,4-trans-cyclohexanediyl (ie, polymerizable liquid crystal compound (1-1)), they are usually 1 and G 2 The polymerizable liquid crystal compound (1-2) in which at least one of the polymerizable liquid crystal compounds (1-2) is 1,4-cis-cyclohexanediyl has a relatively stable molecular structure and is easy to align in the desired direction, so an optical film with fewer orientation defects can be manufactured. Therefore, from the viewpoint of orientation and optical properties, it is considered that the polymerizable liquid crystal compound (1-1) is advantageous as a polymerizable liquid crystal compound represented by formula (1). In the present invention, by making the amount of the polymerizable liquid crystal compound (1-2) relative to the polymerizable liquid crystal compound (1-1) within a specific range, the solubility of the polymerizable liquid crystal compound (1-1) in the solvent can be fully improved without affecting the orientation of the polymerizable liquid crystal compound (1-1).
[0132] If the area percentage value of the polymerizable liquid crystal compound (1-2) is lower than the above lower limit, it is difficult to improve the solubility of the polymerizable liquid crystal compound (1-1) in the solvent, but if the area percentage value of the polymerizable liquid crystal compound (1-2) is above the above lower limit, there is a tendency for the solubility of the polymerizable liquid crystal compound (1-1) in the solvent to be fully improved. In addition, if the area percentage value of the polymerizable liquid crystal compound (1-2) is below the above upper limit, the orientation state of the liquid crystal when an optical film such as a phase difference film is made from a polymerizable liquid crystal composition containing the polymerizable liquid crystal compound can be kept good, so that the orientation defects can be suppressed and an optical film with excellent optical properties can be obtained. In the present invention, the area percentage value of the polymerizable liquid crystal compound (1-2) is more preferably 9% or less, more preferably 8% or less, particularly preferably 7% or less, and particularly preferably 6% or less. In the present invention, the area percentage value of the above-mentioned polymerizable liquid crystal compound (1-2) is preferably 0.1% or more, more preferably 0.5%, and more preferably 2.5% or more. On the other hand, in the present invention, even when a small amount of polymerizable liquid crystal compound (1-2) is contained, the effect of greatly improving the solubility of the polymerizable liquid crystal compound (1-1) in the solvent is excellent. Therefore, in one embodiment of the present invention, the area percentage value of the polymerizable liquid crystal compound (1-2) can be lower than 1.0%. For example, even when it is below 0.5% or below 0.1%, it is easy to fully obtain the above-mentioned advantageous effects in the present invention.
[0133] It should be noted that, in the case of including a plurality of polymerizable liquid crystal compounds belonging to polymerizable liquid crystal compounds (1-1) and / or polymerizable liquid crystal compounds (1-2), the area percentage value of the polymerizable liquid crystal compound (1-2) can be calculated relative to the total peak area of all polymerizable liquid crystal compounds (1-2) and all polymerizable liquid crystal compounds (1-1). The area percentage value can be calculated based on the peak area measured by liquid chromatography, and in detail, it can be measured and calculated by the method described in the embodiments described later.
[0134] The method for producing the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) represented by formula (1) constituting the polymerizable liquid crystal composition of the present invention is not particularly limited, and the polymerizable liquid crystal compound can be produced by appropriately combining known organic synthesis reactions described in organic chemistry methods (Methoden der Organischen Chemie), organic reactions (Organic Reactions), organic synthesis (Organic Syntheses), intermediate organic chemistry (Comprehensive Organic Synthesis), new experimental chemistry lectures, etc. (for example, condensation reaction, esterification reaction, Williamson etherification reaction (Williamson reaction), Ullmann reaction, Wittig reaction, Schiff base synthesis reaction, benzylation reaction, Sonogashira reaction, Suzuki-Miyaura reaction, Negishi reaction, Kumada reaction, Hiyama reaction, Buchwald-Hartwig reaction (Buchwald-Hartwig reaction), Friedel-Crafts reaction, Heck reaction, aldol condensation reaction, etc.) according to its structure.
[0135] For example, D in formula (1) 1 and D 2 is *-O-CO- (* indicates a bonding portion with Ar), G 1 and G 2 is a 1,4-trans-cyclohexanediyl group having a symmetrical structure with Ar as the center (i.e., E 1 With E 2 , A 1 With A 2 , B 1 With B 2 、F 1 With F 2 , P 1 With P 2 The polymerizable liquid crystal compound (1-1) represented by the following formula (A-1) can be produced by an esterification reaction of an alcohol compound (B) represented by the formula (B) and a carboxylic acid compound (C) represented by the formula (C).
[0136] [Chemical formula 14]
[0137]
[0138] HO-Ar-OH (B)
[0139] [Chemical formula 15]
[0140]
[0141] It should be noted that Ar, E in the above formula (A-1), formula (B) and formula (C) 1 、E 2 , A 1 , A 2 , B 1 , B 2 、F 1 、F 2 , P 1 and P 2 The meanings are the same as those defined by the above formula (1), and can be determined corresponding to the structure of the polymerizable liquid crystal compound (1-1) represented by the formula (A-1).
[0142] As the alcohol compound (B), any compound having two hydroxyl groups bonded to the aromatic group Ar corresponding to the aromatic group Ar in the formula (1) in the desired polymerizable liquid crystal compound (1-1) may be used. The aromatic group Ar is the same as Ar specified above, for example, compounds in which the two * parts in the above formulas (2-1) to (2-5) are hydroxyl groups.
[0143] As the carboxylic acid compound (C), any compound which is compatible with P in the formula (1) in the desired polymerizable liquid crystal compound (1-1) is 1 -F 1 -B 1 -A 1 -E 1 -G 1 - The corresponding structure G 1 The compound may be a compound in which a carboxyl group is bonded to the bonded 1,4-trans-cyclohexanediyl group.
[0144] G in formula (1) 1 and G 2 The polymerizable liquid crystal compound (1-2a) in which any one of them is 1,4-cis-cyclohexanediyl can be produced, for example, by reacting the aforementioned alcohol compound (B) with the aforementioned carboxylic acid compound (C) to obtain a compound represented by the following formula (D), and reacting the compound with a carboxylic acid compound (C') represented by the following formula (C').
[0145] [Chemical formula 16]
[0146]
[0147] [Chemical formula 17]
[0148]
[0149] It should be noted that Ar, E in the above formula (C') and (D) 1 、E 2 , A 1, A 2 , B 1 , B 2 、F 1 、F 2 , P 1 and P 2 The meanings are the same as those defined by the above formula (1), and can be determined corresponding to the structure of the polymerizable liquid crystal compound (1-1) represented by the formula (A-1).
[0150] In addition, G in formula (1) 1 and G 2 The polymerizable liquid crystal compound (1-2b) containing only 1,4-cis-cyclohexanediyl groups can be produced, for example, by using a carboxylic acid compound (C′) instead of the carboxylic acid compound (C) in the method exemplified as the method for producing the polymerizable liquid crystal compound (1-1).
[0151] The esterification reaction of the alcohol compound (B) and the carboxylic acid compound (C) and / or the carboxylic acid compound (C′) is preferably carried out in the presence of a condensing agent. By carrying out the esterification reaction in the presence of a condensing agent, the esterification reaction can be carried out efficiently and rapidly.
[0152] Examples of the condensing agent include 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide methyl p-toluenesulfonate, dicyclohexylcarbodiimide, diisopropylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (water-soluble carbodiimide: commercially available as WSC), bis(2,6-diisopropylphenyl)carbodiimide, Carbodiimide, and carbodiimide compounds such as bis(trimethylsilyl)carbodiimide, 2-methyl-6-nitrobenzoic anhydride, 2,2'-carbonylbis-1H-imidazole, 1,1'-oxalyldiimidazole, diphenylphosphoryl azide, 1-(4-nitrobenzenesulfonyl)-1H-1,2,4-triazole, 1H-benzotriazol-1-yloxytripyrrolidinylphosphonium hexafluorophosphate, 1H-benzotriazol-1-yl Oxytris(dimethylamino)phosphonium hexafluorophosphate, N,N,N',N'-tetramethyl-O-(N-succinimidyl)uronium tetrafluoroborate, N-(1,2,2,2-tetrachloroethoxycarbonyloxy)succinimide, N-benzyloxycarbonylsuccinimide, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate 2-Chloro-1,3-dimethylimidazolinium chloride, 2-chloro-1,3-dimethylimidazolinium hexafluorophosphate, 2-chloro-1-methylpyridinium iodide, 2-chloro-1-methylpyridinium p-toluenesulfonate, 2-fluoro-1-methylpyridinium p-toluenesulfonate and pentachlorophenyl trichloroacetate.
[0153] For the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) constituting the polymerizable liquid crystal composition of the present invention, each compound can be prepared separately and then mixed to be used in the form of a liquid crystal mixture. In addition, the reactive group R of the compound represented by the following formula (I) can also be used. 2 , the reactive group R of the compound represented by formula (II) 2 , and R of the compound represented by formula (III) 1 The method of carrying out the reaction step is prepared in the form of a liquid crystal mixture containing the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2a) and / or the polymerizable liquid crystal compound (1-2b).
[0154] [Chemical formula 18]
[0155]
[0156]
[0157] R 1 -Ar-R 1 (III)
[0158] 〔In the formula, R 1 and R 2 represent, independently of one another, reactive groups,
[0159] Ar, E 1 、E 2 , A 1 , A 2 , B 1 , B 2 、F 1 、F 2 , P 1 and P 2 It represents the same as Ar and E in formula (1). 1 、E 2 , A 1 , A 2 , B 1 , B 2 、F 1 、F 2 , P 1 and P 2 Same meaning. ]
[0160] In the case of the former method, it is easy to control the contents of the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) in the polymerizable liquid crystal composition. In the case of the latter method, it has the advantages of simple synthesis and more efficient production of the polymerizable liquid crystal composition.
[0161] Ar, E in formula (I), formula (II) and formula (III) 1 、E 2 , A 1 , A 2 , B 1 , B 2 、F 1 、F 2 , P 1 and P 2 The amount can be determined based on the desired molecular structures of the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2).
[0162] R in formula (III) 1 , and R in formula (I) and formula (II) 2 As long as they can react with each other to form D in the formula (1) representing the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2), 1 and D 2 For example, as R 1 and / or R 2 The reactive group represented by R includes hydroxyl, carboxyl, amino, etc., and R is selected according to the reaction used in the production of the polymerizable liquid crystal compound. 1 and R 2 The reactive group represented by .
[0163] From the viewpoints of the easiness of the reaction, the handling properties of the materials, the availability, etc., typically, for example, as the compound represented by formula (III), R in formula (III) is used. 1 An alcohol compound containing a hydroxyl group, and as the compound represented by formula (I) and the compound represented by formula (II), R in formula (I) and formula (II) is used 2 Each carboxylic acid compound is a carboxyl group, and esterification is carried out, thereby being able to manufacture the polymerizable liquid crystal compound (liquid crystal mixture) constituting the polymerizable liquid crystal composition of the present invention. The esterification can be carried out according to the same method as the esterification that can be utilized for manufacturing the polymerizable liquid crystal compound represented by formula (I), for example, the method and conditions described in the above-mentioned method, Japanese Patent Publication No. 2019-003177, etc. can be used.
[0164] By adjusting the amount of the compound represented by formula (I) and the compound represented by formula (II) used in the preparation, the content ratio of the polymerizable liquid crystal compound (1-1), the polymerizable liquid crystal compound (1-2a) and the polymerizable liquid crystal compound (1-2b) in the obtained liquid crystal mixture can be controlled. 1 With R 2The reaction method uses a plurality of carboxylic acid compounds, and a plurality of compounds can be synthesized simultaneously.
[0165] As long as the effect of the present invention is not affected, the polymerizable liquid crystal composition of the present invention may also include polymerizable liquid crystal compounds other than polymerizable liquid crystal compounds (1-1) and polymerizable liquid crystal compounds (1-2). As other polymerizable liquid crystal compounds other than polymerizable liquid crystal compounds (1-1) and polymerizable liquid crystal compounds (1-2), there can be cited polymerizable liquid crystal compounds that do not have a molecular structure represented by formula (1), for example, polymerizable liquid crystal compounds that generally show positive wavelength dispersion when oriented and polymerized, for example, compounds having polymerizable groups in the compounds described in "3.8.6 Network (Completely Cross-linked Type)" and "6.5.1 Liquid Crystal Material b. Polymerizable Nematic Liquid Crystal Material" of Liquid Crystal Handbook (Compiled by Liquid Crystal Handbook Editorial Committee, published by Maruzen Co., Ltd. on October 30, 2001).
[0166] When the polymerizable liquid crystal composition of the present invention contains polymerizable liquid crystal compounds other than the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2), from the viewpoint of obtaining a liquid crystal cured film having a high degree of orientation order, the proportion of the polymerizable liquid crystal compound (1) relative to the total mass of all polymerizable liquid crystal compounds contained in the polymerizable liquid crystal composition is preferably 51% by mass or more, more preferably 70% by mass or more, further preferably 90% by mass or more, and can be 100% by mass.
[0167] When more than two polymerizable liquid crystal compounds (1-1) are included, it is sufficient to include a polymerizable liquid crystal compound (1-2) corresponding to at least one of the polymerizable liquid crystal compounds (1-1). Relative to the total mass of all polymerizable liquid crystal compounds, the content of the polymerizable liquid crystal compound (1-1) containing the corresponding polymerizable liquid crystal compound (1-2) and the corresponding polymerizable liquid crystal compound (1-2) is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.
[0168] Relative to 100 parts by mass of the solid component of the polymerizable liquid crystal composition, the content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition (the total amount of all polymerizable liquid crystal compounds) is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the perspective of the orientation of the obtained liquid crystal cured film. It should be noted that in this specification, the so-called solid component of the polymerizable liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymerizable liquid crystal mixed composition.
[0169] The polymerizable liquid crystal composition of the present invention may further contain additives such as a photopolymerization initiator, an organic solvent, a polymerization inhibitor, a photosensitizer, and a leveling agent in addition to the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2). Each of these components may be used alone or in combination of two or more.
[0170] The polymerizable liquid crystal composition of the present invention preferably includes a polymerization initiator. A polymerization initiator is a compound that generates reactive species by applying heat or light and can initiate a polymerization reaction of a polymerizable liquid crystal or the like. As reactive species, active species such as free radicals, cations or anions can be cited. Among them, from the viewpoint of easy control of the reaction, a photopolymerization initiator that generates free radicals by light irradiation is preferred.
[0171] Examples of the photopolymerization initiator include benzoin compounds, benzophenone compounds, benzyl ketal compounds, α-hydroxyketone compounds, α-aminoketone compounds, triazine compounds, iodonium salts, and sulfonium salts. Specific examples include Irgacure (registered trademark) 907, Irgacure 184, Irgacure 651, Irgacure 819, Irgacure 250, Irgacure 369, Irgacure 379, Irgacure 127, Irgacure 2959, Irgacure 754, and Irgacure 379EG (all manufactured by BASF Japan Co., Ltd.), SEIKUOL BZ, SEIKUOL Z, and SEIKUOL BEE (all manufactured by Seiko Chemical Industries, Ltd.), kayacure BP100 (manufactured by Nippon Kayaku Co., Ltd.), kayacure UVI-6992 (manufactured by DOW), and ADEKA OPTOMER. SP-152, ADEKA OPTOMER SP-170, ADEKA OPTOMER N-1717, ADEKA OPTOMER N-1919, ADEKA ARKLS NCI-831, ADEKA ARKLSNCI-930 (the above are made by ADEKA Co., Ltd.), TAZ-A, TAZ-PP (the above are made by Japan Siber Hegner Co., Ltd.) and TAZ-104 (the above are made by Sanwa Chemical Co., Ltd.).
[0172] In the present invention, the polymerizable liquid crystal composition preferably contains at least one photopolymerization initiator, and may contain two or more photopolymerization initiators.
[0173] The photopolymerization initiator preferably has a maximum absorption wavelength of 300 nm to 400 nm, more preferably 300 nm to 380 nm, in order to fully utilize the energy emitted from the light source and achieve excellent productivity. Among them, α-acetophenone-based polymerization initiators and oxime-based photopolymerization initiators are preferred.
[0174] Examples of the α-acetophenone-based polymerization initiator include 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone, 2-dimethylamino-1-(4-morpholinophenyl)-2-benzyl-1-butanone, and 2-dimethylamino-1-(4-morpholinophenyl)-2-(4-methylphenylmethyl)-1-butanone. More preferred examples include 2-methyl-2-morpholino-1-(4-methylthiophenyl)-1-propanone and 2-dimethylamino-1-(4-morpholinophenyl)-2-benzyl-1-butanone. Examples of commercially available α-acetophenone compounds include Irgacure 369, 379EG, and 907 (all manufactured by BASF Japan Co., Ltd.) and SEIKUOL BEE (manufactured by Seiko Chemical Co., Ltd.).
[0175] Oxime-based photopolymerization initiators generate methyl radicals by irradiating light. Through the methyl radicals, the polymerization of the polymerizable liquid crystal compound in the deep part of the formed liquid crystal cured film is appropriately carried out. In addition, from the viewpoint of more efficiently carrying out the polymerization reaction in the deep part of the formed liquid crystal cured film, it is preferred to use a photopolymerization initiator that can efficiently utilize ultraviolet rays with a wavelength of more than 350nm. As a photopolymerization initiator that can efficiently utilize ultraviolet rays with a wavelength of more than 350nm, triazine compounds and oxime ester carbazole compounds are preferred. From the viewpoint of sensitivity, oxime ester carbazole compounds are more preferred. As oxime ester carbazole compounds, 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyl oxime)], 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone-1-(O-acetyl oxime) and the like can be cited. Examples of commercially available products of oxime ester type carbazole compounds include Irgacure OXE-01, Irgacure OXE-02, and Irgacure OXE-03 (all manufactured by BASF Japan Co., Ltd.), ADEKA OPTOMER N-1919, and ADEKA ARKLS NCI-831 (all manufactured by ADEKA Corporation).
[0176] The amount of the photopolymerization initiator added is usually 0.1 to 30 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, preferably 0.5 to 100 parts by mass, more preferably 1 to 100 parts by mass, preferably 20 to 20 parts by mass, more preferably 15 to 20 parts by mass. Within the above range, the reaction of the polymerizable group is fully carried out, and it is not easy to disturb the orientation of the polymerizable liquid crystal compound.
[0177] In the present invention, the polymerizable liquid crystal composition is usually applied to a substrate in a state dissolved in a solvent, and therefore preferably contains a solvent. As the solvent, it is preferably a solvent capable of dissolving the polymerizable liquid crystal compound constituting the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) and other polymerizable liquid crystal compositions, and it is preferably a solvent that is inactive to the polymerization reaction of the polymerizable liquid crystal compound. Examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone; and the like. These solvents may be used alone or in combination of two or more. Among them, organic solvents are preferred, and alcohol solvents, ester solvents, ketone solvents, chlorine-containing solvents, amide solvents, and aromatic hydrocarbon solvents are more preferred.
[0178] Relative to 100 parts by mass of the polymerizable liquid crystal composition, the content of the solvent in the polymerizable liquid crystal composition is preferably 50 to 98 parts by mass, more preferably 70 to 95 parts by mass. Therefore, the solid content occupied in 100 parts by mass of the polymerizable liquid crystal composition is preferably 2 to 50 parts by mass, more preferably 5 to 30 parts by mass. When the solid content is less than 50 parts by mass, there is a tendency that the viscosity of the polymerizable liquid crystal composition tends to be lower, the thickness of the film becomes roughly uniform, and unevenness is not easy to occur. The above-mentioned solid content can be appropriately determined considering the thickness of the liquid crystal cured film to be manufactured.
[0179] The polymerization reaction of the polymerizable liquid crystal compound can be controlled by adding a polymerization inhibitor. Examples of the polymerization inhibitor include hydroquinone and hydroquinones having substituents such as alkyl ethers; catechols having substituents such as alkyl ethers such as butyl catechol; free radical scavengers such as pyrogallols and 2,2,6,6-tetramethyl-1-piperidinyloxy free radicals; thiophenols; β-naphthylamines and β-naphthols. In order to polymerize the polymerizable liquid crystal compound without disturbing the orientation, the content of the polymerization inhibitor is generally 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0180] In addition, by using a sensitizer, the photopolymerization initiator can be made highly sensitive. Examples of photosensitizers include xanthones such as xanthone and thioxanthone; anthracenes and anthracenes having substituents such as alkyl ethers; phenothiazines; and rubrene. Examples of photosensitizers include xanthones such as xanthone and thioxanthone; anthracenes and anthracenes having substituents such as alkyl ethers; phenothiazines; and rubrene. The content of the photosensitizer is generally 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.
[0181] In addition, the polymerizable liquid crystal composition of the present invention may contain a leveling agent. The leveling agent is an additive that has the function of adjusting the fluidity of the polymerizable liquid crystal composition and making the film obtained by coating the composition flatter, and examples thereof include silicone-based, polyacrylate-based, and perfluoroalkyl-based leveling agents. Specific examples include DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, and FZ2123 (all manufactured by Dow Corning Toray Corporation), KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, and KF6001 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF-4446, TSF4452, and TSF4460 (all manufactured by Momentive Materials Japan Co., Ltd.), fluorinert (registered trademark) FC-72, fluorinert FC-40, fluorinert FC-43, fluorinert FC-3283 (all manufactured by Sumitomo 3M Co., Ltd.), MEGAFAC (registered trademark) R-08, MEGAFAC R-30, MEGAFAC R-90, MEGAFAC F-410, MEGAFAC F-411, MEGAFAC F-443, MEGAFAC F-445, MEGAFAC F-470, MEGAFAC F-477, MEGAFAC F-479, MEGAFAC F-482, MEGAFAC F-483 (all manufactured by DIC Corporation), EFTOP (trade name) EF301, EFTOP EF303, EFTOP EF351, EFTOP EF352 (all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Surflon (registered trademark) S-381, Surflon S-382, Surflon S-383, Surflon S-393, Surflon SC-101, Surflon SC-105, KH-40, SA-100 (all manufactured by AGC Seimi Chemical Co., Ltd.), trade name E1830, trade name E5844 (manufactured by Daikin Fine Chemicals Laboratories), BM-1000, BM-1100, BYK-352, BYK-353 and BYK-361N (all trade names: manufactured by BM Chemie), etc. Among them, polyacrylate-based leveling agents and perfluoroalkyl-based leveling agents are preferred.
[0182] The content of the leveling agent in the polymerizable liquid crystal composition is preferably 0.01 to 5 parts by mass, and more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, it is easy to orient the polymerizable liquid crystal compound, and the resulting liquid crystal cured film tends to become smoother, so it is preferred. The polymerizable liquid crystal composition may contain two or more leveling agents.
[0183] The polymerizable liquid crystal composition of the present invention can be prepared by adding a solvent, a photopolymerization initiator, an inhibitor, a photosensitizer or a leveling agent and other additives as needed to the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2), and stirring and mixing at a predetermined temperature.
[0184] <Phase difference film>
[0185] With regard to the polymerizable liquid crystal composition of the present invention, the solubility of the polymerizable liquid crystal compound in the solvent is high, therefore, the effect of suppressing the generation of orientation defects caused by the precipitation, precipitation, etc. of the polymerizable liquid crystal compound in the undissolved polymerizable liquid crystal compound and the polymerizable liquid crystal compound in storage is excellent. Therefore, by using the polymerizable liquid crystal composition of the present invention, it is possible to carry out film making without reducing the optical characteristics that the polymerizable liquid crystal compound can originally present, and a liquid crystal curing film with excellent optical characteristics can be obtained. Therefore, the present invention also relates to a phase difference film including a liquid crystal curing film, the liquid crystal curing film is a cured product (liquid crystal curing film) of the polymerizable liquid crystal composition of the present invention, and is cured in a state where the polymerizable liquid crystal compound in the polymerizable liquid crystal composition is oriented. The phase difference film constituted by the aforementioned liquid crystal curing film can fully present the optical characteristics that the polymerizable liquid crystal compound used can originally play, and can become a phase difference film with high optical performance.
[0186] The liquid crystal cured film constituting the phase difference film of the present invention may be composed of a homopolymer of the polymerizable liquid crystal compound (1-1) and a homopolymer of the polymerizable liquid crystal compound (1-2) in an oriented state, or may be composed of a copolymer of a mixture of the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) in an oriented state. The liquid crystal cured film constituting the phase difference film of the present invention is preferably composed of a copolymer of a mixture of the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) in an oriented state, because the polymerization reaction is easy and a uniform liquid crystal cured film is easily obtained.
[0187] In one embodiment of the present invention, the retardation film of the present invention is constituted by including a liquid crystal cured film which is a cured product of the polymerizable liquid crystal composition of the present invention, and the liquid crystal cured film preferably has optical properties represented by the following formula (i).
[0188] 0.75≤Re(450) / Re(550)<1.0 (i)
[0189] [In formula (i), Re(λ) represents the in-plane retardation value of the liquid crystal cured film at a wavelength of λ nm]
[0190] When the liquid crystal cured film satisfies formula (i), the liquid crystal cured film exhibits so-called reverse wavelength dispersion, that is, the in-plane phase difference value at a short wavelength is smaller than the in-plane phase difference value at a long wavelength. From the perspective of improving the reverse wavelength dispersion and further improving the optical properties of the phase difference film, Re (450) / Re (550) is more preferably 0.76 or more, more preferably 0.78 or more, more preferably 0.92 or less, more preferably 0.90 or less, particularly preferably 0.87 or less, more particularly preferably 0.86 or less, and particularly preferably 0.85 or less.
[0191] In one embodiment of the present invention, the retardation film of the present invention preferably includes a liquid crystal cured film having optical characteristics represented by the following formula (ii).
[0192] 1.00≤Re(650) / Re(550) (ii)
[0193] [In formula (ii), Re(λ) represents the in-plane retardation value of the retardation film at a wavelength of λ nm]
[0194] From the viewpoint of the optical characteristics of the retardation film, Re(650) / Re(550) is more preferably 1.01 or more, and even more preferably 1.02 or more.
[0195] Moreover, in one aspect of the present invention, it is preferable that the retardation film of the present invention includes a liquid crystal cured film having optical characteristics represented by the following formula (iii).
[0196] 100nm≤Re(550)≤180nm (iii)
[0197] [In formula (iii), Re(λ) represents the in-plane retardation value of the retardation film at a wavelength of λ nm]
[0198] The liquid crystal cured film satisfying the above formula (iii) functions as a λ / 4 plate, and when an elliptically polarizing plate having a retardation film including the liquid crystal cured film is applied to an optical display, etc., the front reflected hue is improved (the effect of suppressing coloration) with excellent effect. The more preferred range of the in-plane retardation value is 120nm≤Re(550)≤170nm, and the further preferred range is 130nm≤Re(550)≤150nm.
[0199] The above-mentioned in-plane phase difference value can be adjusted by the thickness d of the liquid crystal curing film. The in-plane phase difference value is determined by the above-mentioned formula Re(λ)=(nx(λ)-ny(λ))×d. Therefore, in order to obtain the desired in-plane phase difference value (Re(λ): the in-plane phase difference value of the liquid crystal curing film at a wavelength of λ (nm)), it is sufficient to adjust the three-dimensional refractive index and the film thickness d. It should be noted that in the above-mentioned formula, d represents the thickness of the liquid crystal curing film as the object, nx represents the main refractive index at a wavelength of λnm in the refractive index ellipsoid formed by the liquid crystal curing film in a direction parallel to the plane of the liquid crystal curing film, and ny represents the refractive index at a wavelength of λnm in the refractive index ellipsoid formed by the liquid crystal curing film in a direction parallel to the plane of the liquid crystal curing film and orthogonal to the direction of the above-mentioned nx.
[0200] The retardation film of the present invention can be produced, for example, by a method including the following steps:
[0201] A step of forming a coating film of the polymerizable liquid crystal composition of the present invention, drying the coating film, and aligning the polymerizable liquid crystal compound in the polymerizable liquid crystal composition; and
[0202] A step of polymerizing a polymerizable liquid crystal compound by irradiating light while maintaining the aligned state to form a liquid crystal cured film.
[0203] The coating film of the polymerizable liquid crystal composition can be formed by applying the polymerizable liquid crystal composition on a substrate or an alignment film described later.
[0204] As the substrate, for example, a glass substrate, a film substrate, etc. can be cited. From the viewpoint of processability, a resin film substrate is preferred. As the resin constituting the film substrate, for example, polyolefins such as polyethylene, polypropylene, and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as cellulose triacetate, cellulose diacetate, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; plastics such as polyphenylene sulfide and polyphenylene ether. Such resins can be made into a substrate by film-forming by known means such as solvent casting method and melt extrusion method. On the surface of the substrate, there can be a protective layer formed by acrylic resin, methacrylic resin, epoxy resin, oxetane resin, polyurethane resin, melamine resin, etc., and surface treatments such as mold release treatment, corona treatment, and plasma treatment such as silicone treatment can also be implemented.
[0205] As the substrate, commercially available products can be used. Examples of commercially available cellulose ester substrates include cellulose ester substrates manufactured by Fuji Photo Film Co., Ltd. such as Fujitack Film; cellulose ester substrates manufactured by Konica Minolta Opto Co., Ltd. such as "KC8UX2M", "KC8UY", and "KC4UY", etc. Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona (Germany) such as "Topas (registered trademark)"; cyclic olefin resins manufactured by JSR Corporation such as "ARTON (registered trademark)"; cyclic olefin resins manufactured by Zeon Co., Ltd. such as "ZEONOR (Registered Trademark)" and "ZEONEX (Registered Trademark)"; and cyclic olefin resins manufactured by Mitsui Chemicals, Inc. such as "Apel (Registered Trademark). Commercially available cyclic olefin resin substrates may also be used. Examples of commercially available cyclic olefin resin substrates include cyclic olefin resin substrates such as "Escena (registered trademark)" and "SCA40 (registered trademark)" manufactured by Sekisui Chemical Co., Ltd.; cyclic olefin resin substrates such as "ZEONORFILM (registered trademark)" manufactured by OPTES Co., Ltd.; and cyclic olefin resin substrates such as "ARTONFILM (registered trademark)" manufactured by JSR Co., Ltd.
[0206] The thickness of the substrate is usually 5 to 300 μm, preferably 10 to 150 μm, from the viewpoints of thinning of the retardation film, ease of peeling of the substrate, and handleability of the substrate.
[0207] Examples of a method for applying the polymerizable liquid crystal composition to a substrate include known methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and coater coating, and printing methods such as flexographic printing.
[0208] Then, the solvent is removed by drying, etc., thereby forming a dry coating. As a drying method, natural drying, ventilation drying, heating drying and reduced pressure drying methods, etc. can be cited. At this time, by heating the coating obtained by the polymerizable liquid crystal composition, the polymerizable liquid crystal compound can be oriented in a desired direction (for example, horizontal or vertical direction) relative to the coating plane while the solvent is dried and removed from the coating. The heating temperature of the coating can be appropriately determined considering the materials of the polymerizable liquid crystal compound used and the substrate to be formed, etc., in order to make the polymerizable liquid crystal compound phase change into a liquid crystal phase state, it is generally necessary to be a temperature above the liquid crystal phase transition temperature. In order to remove the solvent contained in the polymerizable liquid crystal composition and make the polymerizable liquid crystal compound become the desired orientation state, for example, it can be heated to a temperature above the liquid crystal phase transition temperature (smectic phase transition temperature or nematic phase transition temperature) of the polymerizable liquid crystal compound contained in the aforementioned polymerizable liquid crystal composition. It should be noted that the liquid crystal phase transition temperature can be measured using, for example, a polarizing microscope with a temperature regulating stage, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), etc. The above-mentioned phase transition temperature of the polymerizable liquid crystal composition of the present invention comprising at least two polymerizable liquid crystal compounds refers to: the temperature measured using a mixture of the following polymerizable liquid crystal compounds, wherein the mixture of the polymerizable liquid crystal compounds is obtained by mixing all the polymerizable liquid crystal compounds constituting the polymerizable liquid crystal composition in the same ratio as the composition in the polymerizable liquid crystal composition.
[0209] The polymerizable liquid crystal composition of the present invention includes at least 2 kinds of polymerizable liquid crystal compounds (1-1) and polymerizable liquid crystal compounds (1-2), and generally, liquid crystal phase transition can be performed at a temperature lower than the temperature at which each individual polymerizable liquid crystal compound (1-1) or polymerizable liquid crystal compound (1-2) is converted into a liquid crystal phase. Therefore, in the manufacture of the phase difference film using the polymerizable liquid crystal composition of the present invention, it is possible to suppress excessive consumption of thermal energy, and it is possible to improve production efficiency. In addition, by being able to perform liquid crystal phase transition with heating at a relatively low temperature, there is also the advantage that the range of selection of the supporting substrate for coating a polymerizable liquid crystal composition is widened.
[0210] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc., and is usually 15 seconds to 10 minutes, preferably 0.5 to 5 minutes.
[0211] The removal of the solvent from the coating can be carried out simultaneously with the heating of the polymerizable liquid crystal compound to a liquid crystal phase transition temperature or above, or it can be carried out independently, but from the viewpoint of improving productivity, it is preferably carried out simultaneously. Before the heating of the polymerizable liquid crystal compound to a liquid crystal phase transition temperature or above is carried out, a pre-drying process for appropriately removing the solvent in the coating under the condition that the polymerizable liquid crystal compound contained in the coating obtained by the polymerizable liquid crystal composition is not polymerized can be provided. As the drying method in the pre-drying process, natural drying method, ventilation drying method, heating drying and reduced pressure drying method, etc. can be cited, and the drying temperature (heating temperature) in the drying process can be appropriately determined according to the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point and its amount, etc.
[0212] Then, in the obtained dry coating, while maintaining the orientation state of the polymerizable liquid crystal compound, the polymerizable liquid crystal compound is polymerized by light irradiation, thereby forming a polymer of the polymerizable liquid crystal compound in the desired orientation state, that is, a liquid crystal cured film. As for the polymerizable liquid crystal composition of the present invention, since it can be highly polymerized by light irradiation of high-intensity ultraviolet rays while suppressing damage to the polymerizable liquid crystal compound, photopolymerization is generally used as a polymerization method. In photopolymerization, the light irradiated to the dry coating can be appropriately selected according to the type of polymerization initiator contained in the dry coating, the type of polymerizable liquid crystal compound and its amount. As a specific example, one or more light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays, and active electron rays can be cited. Among them, from the aspect of easy control of the progress of the polymerization reaction, the device that can be used as a photopolymerization device and widely used in the art is considered, preferably ultraviolet light, preferably in a way that can be photopolymerized using ultraviolet light. The type of polymerizable liquid crystal compound and polymerization initiator contained in the polymerizable liquid crystal composition is pre-selected. In addition, during polymerization, by irradiating light while utilizing appropriate cooling means to cool the dried coating, the polymerization temperature can also be controlled. If the polymerization of polymerizable liquid crystal compound is implemented at a lower temperature by adopting such cooling means, even if a substrate with lower heat resistance is used as a substrate, a liquid crystal cured film can be appropriately formed. In addition, within the range of the unfavorable conditions (deformation of the substrate due to heat, etc.) caused by the heat during light irradiation, the polymerization reaction can also be promoted by increasing the polymerization temperature. During photopolymerization, by shielding, developing, etc., a patterned cured film can also be obtained.
[0213] As the light source of the aforementioned active energy rays, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, and the like.
[0214] UV radiation intensity is usually 10 to 3,000 mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in the wavelength region effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 second to 10 minutes, preferably 0.1 second to 5 minutes, more preferably 0.1 second to 3 minutes, and further preferably 0.1 second to 1 minute. When irradiation is performed once or more times with such an ultraviolet irradiation intensity, the cumulative light amount is 10 to 3,000 mJ / cm 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 .
[0215] The thickness of the liquid crystal cured film can be appropriately selected depending on the optical display to which it is applied, and is preferably 0.2 to 3 μm, and more preferably 0.2 to 2 μm.
[0216] The coating film of the polymerizable liquid crystal composition can be formed on the alignment film. The alignment film has an alignment control force, which makes the polymerizable liquid crystal compound perform liquid crystal orientation in the desired direction. For example, there is an alignment film having an alignment control force that makes the polymerizable liquid crystal compound oriented in the horizontal direction, namely a horizontal alignment film, and an alignment film having an alignment control force that makes the polymerizable liquid crystal compound oriented in the vertical direction, namely a vertical alignment film. The alignment control force can be arbitrarily adjusted by the type, surface state, friction conditions, etc. of the alignment film. When the alignment film is formed by a photo-aligned polymer, it can be arbitrarily adjusted by polarized light irradiation conditions, etc.
[0217] As an alignment film, it is preferred to have solvent resistance that does not dissolve due to the coating of the polymerizable liquid crystal composition, and heat resistance in the heat treatment for the removal of the solvent and the orientation of the polymerizable liquid crystal compound described later. As an alignment film, an alignment film comprising an oriented polymer, a photoalignment film, a groove alignment film having a concave-convex pattern and a plurality of grooves on the surface, a stretched film stretched along the orientation direction, etc. can be cited. From the perspective of the accuracy and quality of the orientation angle, a photoalignment film is preferred.
[0218] As the oriented polymer, for example, polyamides having amide bonds in the molecule, gelatins, polyimides having imide bonds in the molecule and polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates can be cited. Among them, polyvinyl alcohol is preferred. The oriented polymer can be used alone or in combination of two or more.
[0219] An oriented film containing an oriented polymer can be generally obtained by applying a composition obtained by dissolving an oriented polymer in a solvent (hereinafter, sometimes referred to as an "oriented polymer composition") on a substrate and removing the solvent; or by applying the oriented polymer composition on a substrate, removing the solvent, and rubbing (rubbing method). As the solvent, the same solvent as the solvent exemplified above as a solvent that can be used for the polymerizable liquid crystal composition can be cited.
[0220] The concentration of the oriented polymer in the oriented polymer composition may be within a range in which the oriented polymer material can be completely dissolved in the solvent, and is preferably about 0.1 to 20%, more preferably about 0.1 to 10%, based on the solid content of the solution.
[0221] As the oriented polymer composition, a commercially available oriented film material may be used as it is. Examples of commercially available oriented film materials include SUNEVER (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark, manufactured by JSR Corporation).
[0222] As a method for applying the oriented polymer composition to the substrate, the same method as the method exemplified as the method for applying the polymerizable liquid crystal composition to the substrate can be mentioned.
[0223] Examples of a method for removing the solvent contained in the oriented polymer composition include a natural drying method, a ventilation drying method, a heat drying method, and a reduced pressure drying method.
[0224] In order to impart an orientation control force to the oriented film, a rubbing treatment (rubbing method) may be performed as required. As a method of imparting an orientation control force by rubbing, the following method may be cited: a film of an oriented polymer formed on the surface of a substrate by coating an oriented polymer composition on a substrate and annealing the oriented polymer composition is brought into contact with a rubbing roller wound with a rubbing cloth and rotating. During the rubbing treatment, if shielding is performed, multiple regions (patterns) with different orientation directions can also be formed on the oriented film.
[0225] The photo-alignment film can be generally obtained by applying a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film-forming composition") to a substrate, removing the solvent, and then irradiating the substrate with polarized light (preferably polarized UV light). The photo-alignment film is advantageous in that the direction of the orientation control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0226] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by light irradiation. Specifically, groups that participate in the photoreaction of the orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules that occur by light irradiation, which become the source of liquid crystal orientation ability, can be cited. Among them, the group participating in the dimerization reaction or the photocrosslinking reaction is preferred from the aspect of excellent orientation. As a photoreactive group, it is preferably a group having an unsaturated bond, especially a double bond, and it is particularly preferred to have at least one group selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond).
[0227] As photoreactive groups having C=C bonds, vinyl, polyene, stilbene, stilbazole, stilbazolium, chalcone, and cinnamoyl groups can be cited. As photoreactive groups having C=N bonds, groups having structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups having N=N bonds, azophenyl, azonaphthyl, aromatic heterocyclic azo, bisazo, formazan, and groups having an oxidized azobenzene structure can be cited. As photoreactive groups having C=O bonds, benzophenone, coumarin, anthraquinone, and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and halogenated alkyl.
[0228] Among them, photoreactive groups that participate in the photodimerization reaction are preferred, and cinnamoyl and chalcone groups are preferred from the viewpoints that the amount of polarized light irradiation required for photo-alignment is small and a photo-alignment film with excellent thermal stability and temporal stability is easily obtained. As a polymer having a photoreactive group, a polymer having a cinnamoyl group such that the terminal of the polymer side chain is a cinnamic acid structure is particularly preferred.
[0229] By applying the photo-alignment film-forming composition on a substrate, a photo-alignment inducing layer can be formed on the substrate. The solvent contained in the composition may be the same solvent as the solvent previously exemplified as a solvent that can be used in the polymerizable liquid crystal composition, and may be appropriately selected according to the solubility of the polymer or monomer having a photoreactive group.
[0230] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted according to the type of the polymer or monomer and the thickness of the target photo-alignment film, and is preferably set to at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass, relative to the mass of the composition for forming a photo-alignment film. The composition for forming a photo-alignment film may also contain a polymer material such as polyvinyl alcohol and polyimide, and a photosensitizer within a range that does not significantly impair the properties of the photo-alignment film.
[0231] As a method for applying the photo-alignment film-forming composition to a substrate, the same method as the method for applying the oriented polymer composition to a substrate can be cited. As a method for removing the solvent from the applied photo-alignment film-forming composition, for example, natural drying, ventilation drying, heating drying, and reduced pressure drying can be cited.
[0232] When irradiating polarized light, it can be a method of directly irradiating polarized UV light to the product obtained after removing the solvent from the composition for forming a photo-alignment film applied on the substrate, or it can be a method of irradiating polarized light from the substrate side and transmitting the polarized light. In addition, it is particularly preferred that the polarized light is substantially parallel light. The wavelength of the irradiated polarized light is preferably a wavelength in the wavelength region where the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) in the range of 250 to 400 nm is particularly preferred. As the light source used in the polarized light irradiation, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. Among them, high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are preferred because of the large luminous intensity of ultraviolet rays with a wavelength of 313 nm. Polarized UV light can be irradiated by passing light from the aforementioned light source through an appropriate polarizer. As the polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0233] It should be noted that, by shielding during rubbing or polarized light irradiation, a plurality of regions (patterns) in which the directions of liquid crystal alignment are different can be formed.
[0234] The groove oriented film is a film having a concavo-convex pattern or multiple grooves (grooves) on the film surface. When a polymerizable liquid crystal compound is applied to a film having multiple linear grooves arranged at equal intervals, the liquid crystal molecules will be oriented in the direction along the grooves.
[0235] Methods for obtaining a grooved oriented film include: a method of exposing the surface of a photosensitive polyimide film through an exposure mask having a slit in a pattern shape, and then developing and rinsing to form a concave-convex pattern; a method of forming a layer of a UV-curable resin before curing on a plate-like original plate having grooves on its surface, transferring the formed resin layer to a substrate, and then curing the layer; and a method of pressing a roll-like original plate having a plurality of grooves against a film of a UV-curable resin before curing formed on a substrate to form concave-convex patterns, and then curing the layer.
[0236] The thickness of the alignment film (alignment film or photoalignment film containing an aligning polymer) is usually in the range of 10 to 10000 nm, preferably 10 to 1000 nm, more preferably 10 to 500 nm or less, further preferably 10 to 300 nm, particularly preferably 50 to 250 nm.
[0237] <Elliptical polarizing plate>
[0238] The present invention includes an elliptically polarizing plate including the retardation film of the present invention. The elliptically polarizing plate of the present invention includes the retardation film of the present invention and a polarizing film.
[0239] The polarizing film includes a film having a polarizing function, a stretched film adsorbed with a dye having absorption anisotropy, a film including a film coated with a dye having absorption anisotropy as a polarizer, etc. As the dye having absorption anisotropy, for example, a dichroic dye can be mentioned.
[0240] For a film that includes a stretched film adsorbed with a dye having absorption anisotropy as a polarizer, it is usually made by clamping a transparent protective film with an adhesive on at least one side of the following polarizer, and the polarizer is manufactured through the following steps: a step of uniaxially stretching a polyvinyl alcohol resin film; a step of dyeing the polyvinyl alcohol resin film with a dichroic dye so that it adsorbs the dichroic dye; a step of treating the polyvinyl alcohol resin film adsorbed with the dichroic dye with an aqueous boric acid solution; and a step of washing with water after the treatment with the aqueous boric acid solution.
[0241] The polyvinyl alcohol resin is obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith can be used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.
[0242] The saponification degree of the polyvinyl alcohol resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes may be used. The degree of polymerization of the polyvinyl alcohol resin is usually about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.
[0243] The film made of such a polyvinyl alcohol resin can be used as a raw film of a polarizing film. The method of forming the polyvinyl alcohol resin into a film is not particularly limited, and the film can be formed by a known method. The film thickness of the polyvinyl alcohol raw film can be, for example, about 10 to 150 μm.
[0244] The uniaxial stretching of the polyvinyl alcohol resin film can be performed before, at the same time as, or after dyeing based on a dichroic pigment. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. In addition, the uniaxial stretching can be performed in multiple stages thereof. When the uniaxial stretching is performed, the uniaxial stretching can be performed between rollers having different peripheral speeds, or the uniaxial stretching can be performed using a hot roller. In addition, the uniaxial stretching can be dry stretching performed in the atmosphere, or wet stretching performed in a state where the polyvinyl alcohol resin film is swollen with a solvent. The stretching ratio is usually about 3 to 8 times.
[0245] The polyvinyl alcohol-based resin film can be dyed with a dichroic dye by, for example, a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing a dichroic dye.
[0246] As the dichroic pigment, specifically, iodine and dichroic organic dyes can be used. As the dichroic organic dyes, dichroic direct dyes formed by disazo compounds such as CI Direct Red (DIRECT RED) 39, and dichroic direct dyes formed by compounds such as triazo and tetrakis azo can be cited. For the polyvinyl alcohol-based resin film, it is preferably immersed in water before dyeing.
[0247] When iodine is used as a dichroic pigment, a method of dyeing a polyvinyl alcohol-based resin film by immersing it in an aqueous solution containing iodine and potassium iodide can generally be adopted. The content of iodine in the aqueous solution is generally about 0.01 to 1 part by mass relative to 100 parts by mass of water. In addition, the content of potassium iodide is generally about 0.5 to 20 parts by mass relative to 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is generally about 20 to 40°C. In addition, the immersion time (dyeing time) in the aqueous solution is generally about 20 to 1,800 seconds.
[0248] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of dyeing the polyvinyl alcohol-based resin film by immersing the film in an aqueous solution containing a water-soluble dichroic dye can be generally adopted. The content of the dichroic organic dye in the aqueous solution is generally 1×10 -4 ~10 parts by mass, preferably 1×10 -3 ~1 mass part, more preferably 1×10 -3 ~1×10 -2 The aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing auxiliary. The temperature of the dichroic dye aqueous solution used for dyeing is usually about 20 to 80° C. In addition, the immersion time (dyeing time) in the aqueous solution is usually about 10 to 1,800 seconds.
[0249] Boric acid treatment after dyeing based on dichroic pigments can usually be carried out by immersing the dyed polyvinyl alcohol-based resin film in an aqueous solution of boric acid. The content of boric acid in the aqueous solution of boric acid is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. When iodine is used as a dichroic pigment, the aqueous solution of boric acid preferably contains potassium iodide, and the content of potassium iodide at this time is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, relative to 100 parts by mass of water. The immersion time in the aqueous solution of boric acid is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0250] Generally, the polyvinyl alcohol-based resin film treated with boric acid can be subjected to a water washing treatment. The water washing treatment can be performed, for example, by immersing the polyvinyl alcohol-based resin film treated with boric acid in water. The temperature of water in the water washing treatment is generally about 5 to 40° C. In addition, the immersion time is generally about 1 to 120 seconds.
[0251] A drying process can be performed after washing to obtain a polarizer. The drying process can be performed using, for example, a hot air dryer or a far infrared heater. The temperature of the drying process is usually about 30 to 100° C., preferably 50 to 80° C. The time of the drying process is usually about 60 to 600 seconds, preferably 120 to 600 seconds. By drying, the moisture content of the polarizer can be reduced to a practical level. The moisture content is usually about 5 to 20% by mass, preferably 8 to 15% by mass. When the moisture content is within the above range, it is easy to obtain a polarizer with moderate flexibility and excellent thermal stability.
[0252] The thickness of the polarizer obtained by uniaxially stretching the polyvinyl alcohol-based resin film, dyeing it with a dichroic dye, treating it with boric acid, washing it with water, and drying it as described above is preferably 5 to 40 μm.
[0253] As a film formed by coating a pigment having absorption anisotropy, a film obtained by coating a composition containing a dichroic pigment having liquid crystal properties or a composition containing a dichroic pigment and a polymerizable liquid crystal compound, etc. can be cited. The film preferably has a protective film on one or both sides. As the protective film, a film similar to the resin film exemplified in the above text as a base material that can be used in the manufacture of liquid crystal cured film can be cited.
[0254] The thinner the film formed by coating the dye having absorption anisotropy is, the better. From the viewpoint of strength and processability, the thickness of the film is usually 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.
[0255] Specific examples of the film formed by coating a dye having absorption anisotropy include films described in JP-A-2013-33249 and the like.
[0256] By laminating a transparent protective film via an adhesive on at least one side of the polarizer obtained as described above, a polarizing film can be obtained. As the transparent protective film, a transparent film similar to the resin film exemplified above as a substrate that can be used in the manufacture of the liquid crystal cured film constituting the phase difference film can be preferably used.
[0257] The elliptically polarizing plate of the present invention comprises the retardation film of the present invention and a polarizing film, and can be obtained, for example, by laminating the retardation film of the present invention and the polarizing film via an adhesive layer or a pressure-sensitive adhesive layer.
[0258] In one embodiment of the present invention, when the retardation film of the present invention including a liquid crystal cured film is laminated with a polarizing film, it is preferred that the angle formed by the slow axis (optical axis) of the liquid crystal cured film constituting the retardation film and the absorption axis of the polarizing film be 45±5°.
[0259] The elliptically polarizing plate of the present invention may have a structure as that of conventional elliptically polarizing plates, polarizing films, and phase difference films. As such a structure, for example, an adhesive layer (sheet) for attaching the elliptically polarizing plate to a display element constituting an optical display, a protective film used to protect the surface of the polarizing film and the phase difference film from damage or contamination, etc. may be cited.
[0260] The elliptically polarizing plate of the present invention can be used in various display devices, especially optical displays.
[0261] A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. As display devices, there can be cited liquid crystal display devices, organic electroluminescent (EL) display devices, inorganic electroluminescent (EL) display devices, flexible image display devices, touch panel display devices, electron emission display devices (such as field emission display devices (FED), surface field emission display devices (SED)), electronic paper (display devices using electronic ink, electrophoretic elements, plasma display devices, projection display devices (such as grating light valve (GLV) display devices, display devices with digital micromirror devices (DMD)) and piezoelectric ceramic displays. Liquid crystal display devices include any of transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, reflective liquid crystal display devices, direct-view liquid crystal display devices and projection liquid crystal display devices. These display devices can be display devices that display two-dimensional images or stereoscopic display devices that display three-dimensional images. In particular, the elliptically polarizing plate of the present invention can be suitably used in organic electroluminescent (EL) display devices and inorganic electroluminescent (EL) display devices. These display devices (optical displays) can present good image display characteristics by having the elliptically polarizing plate of the present invention having excellent optical properties.
[0262] The flexible image display device including the elliptically polarizing plate of the present invention preferably further includes a window and a touch panel touch sensor.
[0263] The flexible image display device is formed, for example, by a laminate for a flexible image display device and an organic EL display panel, and the laminate for a flexible image display device is arranged on the viewing side relative to the organic EL display panel, and is configured in a bendable manner. As a laminate for a flexible image display device, in addition to the elliptically polarizing plate of the present invention described above, a window, a touch panel touch sensor, etc. may also be included. The stacking order of them is arbitrary, but it is preferred to stack them in the order of window, elliptically polarizing plate, touch panel touch sensor, or window, touch panel touch sensor, elliptically polarizing plate from the viewing side.
[0264] When there is an elliptically polarizing plate on the viewing side of the touch panel touch sensor, the pattern of the touch panel touch sensor is not easily visually recognized, and the visibility of the displayed image is improved, so it is preferred. The various components can be stacked using adhesives, adhesives, etc. In addition, the laminate for the flexible image display device can have a shading pattern formed on at least one side of any layer of the aforementioned window, elliptically polarizing plate, and touch panel touch sensor.
[0265] The window is arranged on the viewing side of the flexible image display device, and is responsible for protecting other components from external impact or environmental changes such as temperature and humidity. In the past, glass was used as such a protective layer, but the window in the flexible image display device is not rigid and hard like glass, but has flexible characteristics. The aforementioned window is formed of a flexible transparent substrate and may include a hard coating on at least one side.
[0266] The transparent substrate preferably has a visible light transmittance of 70% or more, and more preferably has a visible light transmittance of 80% or more. As the transparent substrate, any polymer film having transparency can be used. Among them, polyamide film, polyamide-imide film or polyimide film, polyester film, olefin film, acrylic film, cellulose film with excellent transparency and heat resistance are preferred. It is also preferred to disperse inorganic particles such as silicon dioxide, organic microparticles, rubber particles, etc. in the polymer film.
[0267] The thickness of the transparent substrate is preferably 5 to 200 μm, more preferably 20 to 100 μm.
[0268] A hard coating layer may be provided on at least one side of the transparent substrate constituting the window. The thickness of the hard coating layer is not particularly limited, and may be, for example, 2 to 100 μm. When the thickness of the hard coating layer is within the above range, sufficient impact resistance, scratch resistance, and bending resistance can be easily ensured.
[0269] The hard coating layer can be formed by curing a hard coating layer-forming composition containing a reactive material that forms a cross-linked structure by irradiating active energy rays or thermal energy, but preferably a hard coating layer formed by curing with active energy rays. The so-called active energy rays are defined as energy rays that can decompose compounds that produce active species to produce active species. As active energy rays, visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays and electron rays can be cited, and ultraviolet rays are particularly preferred. The hard coating layer-forming composition usually contains at least one compound of a free radical polymerizable compound and a cationic polymerizable compound, and a polymerization initiator. There are no particular restrictions on free radical polymerizable compounds, cationic polymerizable compounds and polymerization initiators, and previously known substances can be cited. Furthermore, the hard coating layer composition may also contain one or more selected from the group consisting of solvents and additives. As long as the solvent can dissolve or disperse the polymerizable compound and the polymerization initiator, a solvent known as a solvent for a composition for forming a hard coating layer in the field of optical films can be used without restriction. Examples of the additives include inorganic particles, leveling agents, stabilizers, surfactants, antistatic agents, lubricants, and antifouling agents.
[0270] The touch panel touch sensor is used as an input mechanism. As a touch panel touch sensor, various methods such as a resistive film method, a surface elastic wave method, an infrared method, an electromagnetic induction method, and an electrostatic capacitance method have been proposed, and any method can be used. Among them, the electrostatic capacitance method is preferred. The electrostatic capacitance method touch panel touch sensor can be divided into an active area and an inactive area located at the periphery of the aforementioned active area. The active area is an area corresponding to the area (display part) where the screen is displayed on the display panel, and is an area that senses the user's touch, and the inactive area is an area corresponding to the area (non-display part) where the screen is not displayed in the display device. The touch panel touch sensor may include: a substrate with flexible characteristics; a sensing pattern formed in the active area of the aforementioned substrate; and each sensing line formed in the inactive area of the aforementioned substrate and used to connect the aforementioned sensing pattern to an external driving circuit via a pad part.
[0271] There is no particular limitation on the flexible substrate, the sensing pattern, and the sensing lines, and materials applicable in the technical field may be selected from them.
[0272] As a substrate having flexible properties, for example, a substrate made of the same material as the transparent substrate of the aforementioned window can be used. For the substrate of the touch panel touch sensor, a substrate with a toughness of 2,000 MPa% or more is preferred from the perspective of suppressing cracks in the touch panel touch sensor, and a substrate with a toughness of 2,000 MPa% to 30,000 MPa% is more preferred. Here, toughness is defined as the lower area of the curve up to the failure point in the stress (MPa)-strain (%) curve (Stress-strain curve) obtained by the tensile test of the polymer material.
[0273] Each layer (window, elliptically polarizing plate, touch panel touch sensor) forming the aforementioned flexible image display device laminate and the film components (polarizing film, phase difference film, etc.) constituting each layer can be formed using an adhesive. As an adhesive, an aqueous adhesive, an organic solvent system, a solvent-free adhesive, a solid adhesive, a solvent-volatile adhesive, a moisture-curing adhesive, a heat-curing adhesive, an anaerobic curing type, an active energy ray-curing adhesive, a curing agent mixed adhesive, a hot melt adhesive, a pressure-sensitive adhesive (adhesive), a rewetting adhesive, etc. are widely used adhesives. Among them, it is preferred to use an aqueous solvent-volatile adhesive, an active energy ray-curing adhesive, and an adhesive. The thickness of the adhesive layer can be appropriately adjusted according to the required bonding force, etc., and is usually 0.01μm to 500μm, preferably 0.1μm to 300μm. When a plurality of adhesive layers are present in the laminate for a flexible image display device, the type and thickness of the adhesive constituting each adhesive layer may be the same or different.
[0274] Example
[0275] Hereinafter, the present invention will be described in more detail using Examples. It should be noted that, unless otherwise specified, "%" and "parts" in the examples refer to mass % and mass parts, respectively.
[0276] 1. Preparation of polymerizable liquid crystal compounds and liquid crystal mixtures
[0277] Production Example 1: Production of a polymerizable liquid crystal compound represented by formula (A-1)
[0278] A polymerizable liquid crystal compound represented by the following formula (A-1) (hereinafter referred to as “polymerizable liquid crystal compound (A-1)”) was synthesized according to the following route.
[0279] [Chemical formula 19]
[0280]
[0281] A 100 mL four-necked flask equipped with a serpentine condenser and a thermometer was placed in a nitrogen atmosphere, and 11.02 g of the compound (E-1) synthesized in the reference patent document (Japanese Patent Application Laid-Open No. 2010-31223), 4.00 g of the compound (D-1) synthesized in the reference patent document (Japanese Patent Application Laid-Open No. 2011-207765), 0.02 g of DMAP (manufactured by Wako Pure Chemical Industries, Ltd.), 0.20 g of BHT (manufactured by Wako Pure Chemical Industries, Ltd.), and 58 g of chloroform (manufactured by Kanto Chemical Co., Ltd.) were added and mixed, and then 4.05 g of IPC (manufactured by Wako Pure Chemical Industries, Ltd.) was further added using a dropping funnel, and these were reacted at 0°C overnight. After the reaction was completed, the insoluble components were removed by filtration. The obtained chloroform solution was added dropwise to acetonitrile (manufactured by Wako Pure Chemical Industries, Ltd.) in an amount three times the weight of the chloroform contained in the solution to precipitate a solid. Next, the precipitated solid was taken out by filtration, washed three times with 20 g of acetonitrile, and dried under reduced pressure at 30° C., thereby obtaining 11.43 g of polymerizable liquid crystal compound (A-1). The yield of polymerizable liquid crystal compound (A-1) was 80% based on compound (D-1).
[0282] Production Example 2: Production of Liquid Crystal Mixture (A')
[0283] A liquid crystal mixture (hereinafter also referred to as “liquid crystal mixture (A′)”) containing polymerizable liquid crystal compounds represented by the following formulae (A-1) to (A-3) was synthesized according to the following route.
[0284] [Chemical formula 20]
[0285]
[0286] [Chemical formula 21]
[0287]
[0288] With reference to patent document (Japanese Patent Publication No. 2010-31223), trans-1,4-cyclohexanedicarboxylic acid was changed to cis-1,4-cyclohexanedicarboxylic acid and 27.02g of a mixture represented by compound (E-2) was synthesized. Using the substance obtained by mixing the obtained compound (E-2) with compound (E-1) at 10 / 90, the compound (E-1) of Manufacturing Example 1 was changed to the aforementioned mixture of compound (E-2) and compound (E-1) for synthesis, thereby obtaining 10.57g of liquid crystal mixture (A'). The obtained liquid crystal mixture (A') was analyzed by HPLC determination, and as a result, the liquid crystal mixture contained the above-mentioned compound (A-1), compound (A-2) and compound (A-3), and the total peak area of the above-mentioned compound (A-2) and compound (A-3) was 3.00% relative to the total peak area of compound (A-1), compound (A-2) and compound (A-3) as 100%.
[0289] 〔HLPC determination〕
[0290] The HPLC measurement may be performed under any conditions as long as the peak derived from the polymerizable liquid crystal compound can be separated. The HPLC measurement conditions used in the analysis in the examples and comparative examples of the present invention are shown below.
[0291] (Measurement conditions)
[0292] Measurement apparatus: HPLC LC-10AT (manufactured by Shimadzu Corporation)
[0293] Column: L-Column ODS (inner diameter 3.0 mm, length 150 mm, particle size 3 μm)
[0294] Temperature: 40℃
[0295] Mobile phase A: 0.1% (v / v)-TFA / water
[0296] Mobile phase B: 0.1% (v / v)-TFA / acetonitrile
[0297] Gradient: 0min 70%-B
[0298] 30min 100%-B
[0299] 60min 100%-B
[0300] 60.01min 70%-B
[0301] 75min 70%-B
[0302] Flow rate: 0.5mL / min
[0303] Injection volume: 5μL
[0304] Detection wavelength: 254nm
[0305] Production Example 3: Production of a polymerizable liquid crystal compound represented by formula (B-1)
[0306] A polymerizable liquid crystal compound represented by the following formula (B-1) (hereinafter referred to as “polymerizable liquid crystal compound (B-1)”) was synthesized according to the following route.
[0307] [Chemical formula 22]
[0308]
[0309] The reaction was carried out in the same manner as in Preparation Example 1 except that 4.22 g of the compound (D-2) was used to obtain 11.75 g of the polymerizable liquid crystal compound (B-1). The yield of the polymerizable liquid crystal compound (B-1) was 81% based on the compound (D-2).
[0310] Production Example 4: Production of Liquid Crystal Mixture (B')
[0311] A liquid crystal mixture (hereinafter also referred to as “liquid crystal mixture (B′)”) containing polymerizable liquid crystal compounds represented by the following formulae (B-1) to (B-3) was synthesized according to the following route.
[0312] [Chemical formula 23]
[0313]
[0314] Except for changing to 4.22 g of compound (D-2), all the reactions were carried out in the same manner as described in Preparation Example 2 to obtain 10.88 g of a liquid crystal mixture (B'). The obtained liquid crystal mixture (B') was analyzed under the above-mentioned HPLC measurement conditions. As a result, the liquid crystal mixture contained the above-mentioned compound (B-1), compound (B-2) and compound (B-3), and the total peak area of the above-mentioned compound (B-2) and compound (B-3) was 5.23% relative to the total peak area of compound (B-1), compound (B-2) and compound (B-3) of 100%.
[0315] Production Example 5: Production of Liquid Crystal Mixture (C')
[0316] Except that the mixing ratio of compound (E-2) and compound (E-1) used in Preparation Example 4 was changed to 20 / 80, the reaction was carried out in the same manner as described in Preparation Example 4 to obtain 10.44 g of a liquid crystal mixture (C'). The obtained liquid crystal mixture (C') was analyzed under the above-mentioned HPLC measurement conditions. As a result, the liquid crystal mixture contained the above-mentioned compound (B-1), compound (B-2) and compound (B-3), and the total peak area of the above-mentioned compound (B-2) and compound (B-3) was 12.3% relative to the total peak area of compound (B-1), compound (B-2) and compound (B-3) (100%).
[0317] It should be noted that in the above-mentioned manufacturing examples 1 to 5, compound (A-1) and compound (B-1) each belong to the polymerizable liquid crystal compound (1-1) in the present invention, compound (A-2) and compound (B-2) each belong to the polymerizable liquid crystal compound (1-2a) in the present invention, and compound (A-3) and compound (B-3) each belong to the polymerizable liquid crystal compound (1-2b) in the present invention.
[0318] 2. Polymerizable Liquid Crystal Compounds / Mixtures of Examples and Comparative Examples
[0319] (1) Example 1: Preparation of Liquid Crystal Mixture (1)
[0320] The liquid crystal mixture (A') obtained in the above-mentioned Production Example 2 is mixed with the polymerizable liquid crystal compound (A-1) obtained in the above-mentioned Production Example 1 in such a manner that the peak area of the compound (A-2) and the compound (A-3) becomes 0.1% relative to the total peak area of 100% of the compound (A-1), the compound (A-2) and the compound (A-3) under the above-mentioned HPLC measurement conditions to obtain a liquid crystal mixture (1).
[0321] (2) Example 2: The liquid crystal mixture (A') obtained in the above-mentioned Production Example 2 was used as liquid crystal mixture (2).
[0322] (3) Example 3: Preparation of Liquid Crystal Mixture (4)
[0323] The liquid crystal mixture (B') obtained in Preparation Example 4 is mixed with the polymerizable liquid crystal compound (B-1) obtained in the above-mentioned Preparation Example 3 in such a manner that the peak area of compound (B-2) and compound (B-3) becomes 0.4% relative to the total peak area of compound (B-1), compound (B-2) and compound (B-3) as 100% under the above-mentioned HPLC measurement conditions to obtain a liquid crystal mixture (3).
[0324] (4) Example 4: The liquid crystal mixture (B') obtained in the above-mentioned Production Example 4 was used as liquid crystal mixture (4).
[0325] (5) Comparative Example 1: The polymerizable liquid crystal compound (A-1) obtained in Production Example 1 was used as the liquid crystal compound (1).
[0326] (6) Comparative Example 2: The polymerizable liquid crystal compound (B-1) obtained in Production Example 3 was used as the liquid crystal compound (2).
[0327] (7) Comparative Example 3: The liquid crystal mixture (C′) obtained in Production Example 5 was used as liquid crystal mixture (5).
[0328] 3. Solubility evaluation
[0329] N-methylpyrrolidone (NMP) and a stirrer were placed in a vial, and the liquid crystal mixtures (1) to (5), liquid crystal compounds (1) and (2) prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were added while stirring with a magnetic stirrer (HS-30DN, ASONE) until dissolved residues were visually confirmed. When dissolved residues were confirmed, the solubility of each liquid crystal mixture and polymerizable liquid crystal compound in NMP was calculated in the form of weight percentage concentration from (weight of each liquid crystal mixture and polymerizable liquid crystal compound) / (weight of each liquid crystal mixture and polymerizable liquid crystal compound + weight of NMP). The results are shown in Table 2.
[0330] 4. Orientation defect evaluation
[0331] (1) Production of optical film (phase difference film)
[0332] An optical film (retardation film) was produced according to the following procedures.
[0333] (i) Preparation of photo-alignment film-forming composition
[0334] The following components were mixed, and the obtained mixture was stirred at 80° C. for 1 hour to obtain a composition for forming a photo-alignment film.
[0335] The photo-alignment material (5 parts) represented by the following formula (number average molecular weight about 28000):
[0336] [Chemical formula 24]
[0337]
[0338] Solvent (95 parts): Cyclopentanone
[0339] (ii) Preparation of polymerizable liquid crystal composition
[0340] A cycloolefin polymer film (COP) (ZF-14, manufactured by Zeon Co., Ltd.) was treated once using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.) at an output of 0.3 kW and a treatment speed of 3 m / min. The photo-alignment film-forming composition was applied to the surface subjected to the corona treatment using a bar coater, dried at 80° C. for 1 minute, and then irradiated with a polarized UV light device (SPOT CURE SP-7; manufactured by USHIO Electric Co., Ltd.) at a rate of 100 mJ / cm 2 Polarized UV light exposure was performed with a cumulative light amount of . The film thickness of the obtained photo-alignment film was measured with a laser microscope (LEXT, manufactured by Olympus Corporation) and found to be 100 nm.
[0341] Next, the liquid crystal mixture (1) prepared in Example 1 was added to the vial bottle, and a photopolymerization initiator, a leveling agent, a polymerization inhibitor and a solvent were added according to the composition described in Table 1. The mixture was stirred at 80° C. for 30 minutes using a carousel to obtain a polymerizable liquid crystal composition.
[0342] In addition, the compounding amount of the solvent was set so that the mass % of the liquid crystal mixture became 13% with respect to the total amount of the polymerizable liquid crystal composition (solution).
[0343] [Table 1]
[0344]
[0345] Polymerization initiator: 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone (Irgacure 369; manufactured by BASF Japan)
[0346] Leveling agent: Polyacrylate compound (BYK-361N; manufactured by BYK Chemie Japan)
[0347] Polymerization inhibitor: BHT (produced by Wako Pure Chemical Industries, Ltd.)
[0348] Solvent: N-methylpyrrolidone (NMP; manufactured by Kanto Chemical Co., Ltd.)
[0349] (iii) Fabrication of optical films
[0350] The obtained polymerizable liquid crystal composition was applied to the alignment film using a bar coater, dried at 120°C for 1 minute, and then irradiated with ultraviolet light (under nitrogen atmosphere, wavelength: 365 nm, cumulative light intensity at wavelength 365 nm: 1000 mJ / cm 2 ), thereby making an optical film.
[0351] In addition, instead of the above-mentioned liquid crystal mixture (1), the liquid crystal mixtures (2) to (5) prepared in Examples 2 to 5 and Comparative Examples 1 to 3, and the liquid crystal compounds (1) and (2) were used respectively, and a photopolymerization initiator, a leveling agent, an inhibitor and a solvent were added according to the composition described in Table 1. Except for this, the same operation was carried out as above to prepare a polymerizable liquid crystal composition and an optical film.
[0352] (2) Evaluation of orientation defects
[0353] The obtained optical film was cut into 10 cm squares, and the number of alignment defects on the screen was visually confirmed using a polarizing microscope (LEXT, manufactured by Olympus Corporation), and evaluated based on the following evaluation criteria.
[0354] (Evaluation criteria for orientation defects)
[0355] 1: Orientation defects (>100) occur on the entire surface
[0356] 2: 11 to 100
[0357] 3: 1 to 10
[0358] 4: No defects
[0359] [Table 2]
[0360]
[0361] As shown in Table 1, it is confirmed that the polymerizable liquid crystal composition (Examples 1 to 4) according to the present invention can suppress orientation defects and improve the solubility of the polymerizable liquid crystal compound (1-1) in the solvent by containing a specific amount of the polymerizable liquid crystal compound (1-2) relative to the polymerizable liquid crystal compound (1-1).
Claims
1. A polymerizable liquid crystal composition comprising at least two polymerizable liquid crystal compounds having the same molecular weight but different molecular structures and represented by formula (1), [Chemical formula 1] p1-F1B1-A1-E1-G1-D1-Ar-D2G2-E2-A2-B2-F2-p2(1) In formula (1), Ar represents a divalent aromatic hydrocarbon group or a divalent aromatic heterocyclic group which may have a substituent, D 1 , D 2 、E 1 、E 2 , B 1 and B 2 Each independently represents -CR 11 R 12 -, -CH2-CH2-, -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -C(=S)-O-, -OC(=S)-, -OC(=S)-O-, -CO-NR 11 -、-NR 11 -CO-, -O-CH2-, -CH2-O-, -S-CH2-, -CH2-S- or a single bond, R 11 and R 12 each independently represents a hydrogen atom, a fluorine atom or an alkyl group having 1 to 4 carbon atoms, G 1 and G 2 Each represents a 1,4-cyclohexanediyl group, A 1 and A 2 Each independently represents a divalent alicyclic hydrocarbon group having 3 to 16 carbon atoms or a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms, wherein the hydrogen atoms contained in the alicyclic hydrocarbon group and the aromatic hydrocarbon group are optionally replaced by halogen atoms, -R 13 、-OR 13 , cyano or nitro substituted, R 13 represents an alkyl group having 1 to 4 carbon atoms, wherein hydrogen atoms contained in the alkyl group are optionally substituted with fluorine atoms, F 1 and F 2 Each independently represents an alkanediyl group having 1 to 12 carbon atoms, wherein the hydrogen atoms contained in the alkanediyl group are optionally replaced by -OR 14 or halogen atom substitution, R 14 represents an alkyl group having 1 to 4 carbon atoms, wherein the hydrogen atoms contained in the alkyl group are optionally substituted by fluorine atoms, and the -CH2- contained in the alkanediyl group is optionally replaced by -O- or -CO-, P1 and P 2 Each independently represents a hydrogen atom or a polymerizable group, wherein, P 1 and P 2 At least one of them is a polymerizable group; In the polymerizable liquid crystal composition, as the polymerizable liquid crystal compound, the polymerizable liquid crystal compound comprises G in formula (1): 1 and G 2 A polymerizable liquid crystal compound (1-1) each of which is a 1,4-trans-cyclohexanediyl group, and a polymerizable liquid crystal compound (1-1) having only G in the formula (1) 1 and G 2 a polymerizable liquid crystal compound (1-2) having a different molecular structure in that at least one of the compounds is a 1,4-cis-cyclohexanediyl group, The ratio of the peak area of the polymerizable liquid crystal compound (1-2) to the total peak area of the polymerizable liquid crystal compound (1-1) and the polymerizable liquid crystal compound (1-2) measured by liquid chromatography is 0.01% to 10%.
2. The polymerizable liquid crystal composition according to claim 1, wherein The polymerizable liquid crystal compound (1-2) comprises G in the formula (1): 1 and G 2 A polymerizable liquid crystal compound (1-2a) in which any one of the above is 1,4-cis-cyclohexanediyl, and G in the formula (1) 1 and G 2 All of them are polymerizable liquid crystal compounds (1-2b) of 1,4-cis-cyclohexanediyl.
3. The polymerizable liquid crystal composition according to claim 1 or 2, wherein: Ar in formula (1) is a group represented by any one of formulas (2-1) to (2-5), [Chemical formula 2] In the formula, * indicates the same as D 1 or D 2 The bonding portion; Q 1 Indicates -S-, -O-, or -NR 15 -, R 15 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent, Q 2 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent; W 1 and W 2 Each independently represents -O-, -S-, -CO-, -NR 15 -, R 15 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent; Y 1 represents an alkyl group having 1 to 6 carbon atoms, an aromatic hydrocarbon group or an aromatic heterocyclic group which may have a substituent, wherein a hydrogen atom contained in the alkyl group, the aromatic hydrocarbon group or the aromatic heterocyclic group may be substituted with a halogen atom, and -CH2- contained in the alkyl group may be replaced with -O-, -CO-, -O-CO- or -CO-O-, Y 2 represents a CN group or an alkyl group having 1 to 12 carbon atoms which may have a substituent, wherein the hydrogen atoms contained in the alkyl group may be substituted by halogen atoms, and the -CH2- contained in the alkyl group may be replaced by -O-, -CO-, -O-CO- or -CO-O-; Z 1 , Z 2 and Z 3 each independently represents a hydrogen atom, an aliphatic hydrocarbon group or alkoxy group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 3 to 20 carbon atoms, a monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -NR 15 R 16 or -SR 15 , optionally, Z 1 and Z 2 bonded to each other to form an aromatic ring or an aromatic heterocyclic ring, R 15 and R 16 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; Ax represents an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocyclic rings, Ay represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a substituent, or an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocyclic rings, and Ax and Ay are optionally bonded to form a ring; Y 3 and Y 4 Each independently represents a group selected from the following formula (Y-1), [Chemical formula 3] In formula (Y-1), M 1 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and the alkyl group may be substituted with one or more substituents X 3 Substitution, Substituent X 3 represents a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a sulfur pentafluoride group, a nitro group, a cyano group, an isocyano group, an amino group, a hydroxyl group, a mercapto group, a methylamino group, a dimethylamino group, a diethylamino group, a diisopropylamino group, a trimethylsilyl group, a dimethylsilyl group, a thioisocyano group, or one -CH2- or two or more non-adjacent -CH2- are each independently optionally replaced by -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NH-CO-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-, and any hydrogen atom in the alkyl group is optionally substituted by a fluorine atom, or is optionally -B 11 -F 11 -P 11 The group represented by B 11 、F 11 and P 11 Each of them is the same as B in the formula (1) 1 、F 1 and P 1 Similarly defined, each with the B 1 、F 1 and P 1 Same or different; U 1 represents an organic group having 2 to 30 carbon atoms and having an aromatic hydrocarbon group, wherein any carbon atom of the aromatic hydrocarbon group is optionally replaced by a heteroatom, and the aromatic hydrocarbon group is optionally substituted by one or more of the substituents X 3 replace; T 1 represents -O-, -S-, -COO-, -OCO-, -OCO-O-, -NU 2 -, -N=CU 2 -, -CO-NU 2 -、-OCO-NU 2 -or-O-NU 2 -,U 2 represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, a cycloalkenyl group having 3 to 12 carbon atoms, an organic group having 2 to 30 carbon atoms and having an aromatic hydrocarbon group in which any carbon atom of the aromatic hydrocarbon group is optionally replaced by a heteroatom, or (E 11 -A 11 ) q -B 12 -F 12 -P 12 The alkyl, cycloalkyl, cycloalkenyl and aromatic hydrocarbon groups are each unsubstituted or substituted with one or more substituents X 3 The alkyl group is optionally substituted by the cycloalkyl or cycloalkenyl group, and optionally, one -CH2- or two or more non-adjacent -CH2- in the alkyl group are each independently replaced by -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -SO2-, -O-CO-O-, -CO-NH-, -NH-CO-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-; optionally, one -CH2- or two or more non-adjacent -CH2- in the cycloalkyl or cycloalkenyl group are each independently replaced by -O-, -CO-, -COO-, -OCO- or -O-CO-O-, E 11 , A 11 , B 12 、F 12 and P 12 Each of them is equal to E in formula (1) 1 , A 1 , B 1 、F 1 and P 1 Similarly defined, each with the E 1 , A 1 , B 1 、F 1 and P 1 are the same or different, q represents an integer from 0 to 4, E 11 and / or A 11 When there are multiple, each is the same or different, optionally, U 1 with U 2 bonded to form a ring.
4. The polymerizable liquid crystal composition according to claim 1 or 2, wherein: A in formula (1) 1 and A 2 Each is independently 1,4-cyclohexanediyl or 1,4-phenylenediyl.
5. The polymerizable liquid crystal composition according to claim 1 or 2, wherein: P in formula (1) 1 and P 2 Each is an acryloyl group. The polymerizable liquid crystal composition according to claim 1 , further comprising a photopolymerization initiator. 7 . The polymerizable liquid crystal composition according to claim 1 , further comprising an organic solvent. 8 . A retardation film comprising a liquid crystal cured film, wherein the liquid crystal cured film is a cured product of the polymerizable liquid crystal composition according to claim 1 .
9. The phase difference film according to claim 8, wherein: The liquid crystal cured film satisfies formula (i): 0.75≤Re(450) / Re(550)<1.00 (i) In the formula (i), Re(λ) represents the in-plane retardation value of the liquid crystal cured film at a wavelength of λ nm. 10 . An elliptically polarizing plate comprising the phase difference film according to claim 8 .
11. An optical display comprising the elliptically polarizing plate according to claim 10. 12 . A flexible image display device comprising the elliptically polarizing plate according to claim 10 .
